Method for manufacturing corrosion inhibitor for boiler, boiler and method for inhibiting corrosion in boiler
The method addresses the inefficiencies in existing corrosion inhibitor production by using a combination of washing, pickling, and alkaline hydrothermal treatments on combustion ash from waste treatment facilities, resulting in a corrosion inhibitor with improved corrosion suppression capabilities and reduced Si and Al content.
Patent Information
- Application Number
- JP2020207141
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-14
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2040-12-14
AI Technical Summary
Existing methods for manufacturing corrosion inhibitors for boilers are inefficient, as they require excessive pickling, leading to the leakage of essential components like Si and Al, and do not effectively remove corrosion factors such as NaCl, KCl, and heavy metals, which are present in fly ash.
A method involving the use of combustion ash from waste treatment facilities, which includes washing and pickling treatments followed by alkaline hydrothermal treatment, to produce a corrosion inhibitor with reduced Si and Al content and enhanced corrosion suppression capabilities.
The method efficiently removes corrosion factors and impurities, reduces the amount of Si and Al sources needed, and produces a corrosion inhibitor with suitable Ca, Al, and Si content, effectively suppressing corrosion in boiler superheater tubes.
Smart Images

Figure 0007655501000014 
Figure 0007655501000015 
Figure 0007655501000016
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for efficiently producing a corrosion inhibitor for boilers, which is intended to inhibit corrosion of boilers, particularly superheater tubes, by recycling combustion ash, such as molten fly ash and combustion fly ash, which have conventionally been treated as industrial waste, and using the recycled ash as a main raw material, and to a boiler and a method for inhibiting corrosion of the boiler. [Background technology]
[0002] Fly ash (incineration fly ash, molten fly ash) discharged from waste treatment facilities is prohibited from being directly disposed of in landfills, and is instead disposed of as ordinary general waste in landfills after intermediate treatment such as melting and solidifying, cement solidification, chemical treatment, and discharge treatment using acids or other solvents. In addition, heavy metals are extracted from incineration fly ash and molten fly ash and reduced at the mine site to recover resources. Specific treatment methods include melting treatment, wet method, and chlorination volatilization method. Zinc, lead, copper, etc. are recovered by these treatment methods. The recovered metals are purified at smelters and reused as metal materials. The recovered slag is reused as a cement raw material and a raw material for steelmaking. The solids other than the recovered slag are reused as raw materials for non-ferrous smelting.
[0003] Landfill disposal has low disposal costs, but serious problems such as the difficulty of securing final disposal sites. Therefore, there is a need to increase the resource recovery rate of combustion fly ash and molten fly ash and reduce the amount of waste disposed at final disposal sites. Landfill reduction has high recycling potential, but high disposal costs.
[0004] As a method for solving the above problems, Patent Document 1 describes a method for recycling the incineration ash produced by incinerating combustible waste, which is washed with water, treated with hydrochloric acid, and then treated with alkali under heating, washed with water to remove the alkali, and then dried to turn it into a material with ion exchange and adsorption capabilities.
[0005] In the boiler superheater tubes (SH tubes) of waste treatment facilities that use biomass fuels, general household waste, waste tires, waste plastics, etc., incineration fly ash that has been washed with water, and molten fly ash as boiler fuel, for example, KCl, NaCl, ZnCl 2 , PbCl 2 , K 2 SO 4 , Na 2 SO 4 Corrosion caused by low-melting-point molten salts such as uranium, tin, and tantalum has become a problem. In addition, it is desirable to increase the steam temperature in order to improve the power generation efficiency of boilers, but the corrosion problem caused by molten salts becomes even more serious as the temperature increases.
[0006] Patent Document 2 describes that the use of a compound containing as a main component at least one element selected from the group consisting of Ca, Si, Al, Mg, and Fe can suppress the progression of corrosion of boiler superheater tubes (SH tubes). [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Japanese Patent Application Publication No. 11-207294 [Patent Document 2] Patent No. 6046886 Summary of the Invention [Problem to be solved by the invention]
[0008] Patent Document 1 describes that a material with increased ion exchange capacity and adsorption capacity can be obtained by performing a water washing treatment, or performing a water washing treatment followed by a hydrochloric acid treatment. If a water washing treatment is performed as a pretreatment before the alkaline hydrothermal treatment, NaCl, KCl, PbCl, etc., which are corrosion factors of boiler superheater tubes, can be removed. 2 , CaCl 2 and Ca(OH), an inhibitor of corrosion inhibitors. 2 In addition, strong pickling can remove ZnO, CuO, PbSiO, etc., which are corrosion factors of boiler superheater tubes.3 etc. can be removed. However, if the pickling treatment is too strong, the components Si and Al necessary for synthesizing the corrosion inhibitor will flow out, making it impossible to synthesize a corrosion inhibitor having a corrosion-inhibiting effect, and therefore it is difficult to apply Patent Document 1 as it is. Furthermore, if Ca is not sufficiently removed by the water washing treatment and hydrochloric acid treatment, the proportion of calcium carbonate produced during the alkaline hydrothermal treatment increases, and the corrosion inhibition effect decreases. Patent Document 1 does not disclose a lower limit for the Ca content of the raw material used in the alkaline hydrothermal treatment. Furthermore, when synthesizing a corrosion inhibitor using incineration fly ash with a low content of Si and Al, it is necessary to remove heavy metals Pb, Zn, and Cu, Ca, Na, K, and Cl while suppressing the elution of Si and Al by water washing and pickling. If the concentration of Si and Al is insufficient, the corrosion inhibitor is not produced or a corrosion inhibitor with a low corrosion inhibition effect is produced. However, Patent Document 1 does not disclose the lower limit of the content of Si and Al in the incineration fly ash used in the alkaline hydrothermal treatment.
[0009] Boiler superheater tubes in waste treatment facilities that use biomass fuels, general household waste, waste tires, waste plastics, etc., incineration fly ash that has been washed with water, and molten fly ash as boiler fuels are in a severe corrosive environment that contains a large amount of heavy metals and Cl, which are corrosion factors, compared to boiler superheater tubes in normal waste incinerators and waste treatment facilities that handle only general household waste. Therefore, the effect of suppressing the corrosion of the boiler superheater tubes is small when a compound containing at least one element selected from Ca, Si, Al, Mg, and Fe as a main component is merely added as a corrosion inhibitor described in Patent Document 2.
[0010] From the above, it has been found that the fly ash from molten waste and incineration fly ash, which are treated as industrial waste and contain a large amount of heavy metals but a small amount of Si and Al, can be extracted while suppressing the elution of Si and Al, which are components of CSH (calcium silicate hydrate) and CASH (calcium aluminosilicate hydrate). It is also possible to extract the corrosion factors that corrode boilers (especially boiler superheater tubes (SH tubes)), such as Na, K, Cl, Pb, Zn, and Cu, as well as the impurities that do not contribute to the synthesis of corrosion inhibitors (NaCl, CaCl 2 It is desirable to produce a corrosion inhibitor that can efficiently remove heavy metals, NaCl, KCl, CaCl, etc., and does not require the addition of Si or Al in the post-acid pickling process. 2 There is a demand for the production of corrosion inhibitors that have corrosion-inhibiting effects even in boiler superheater tubes, which contain a large amount of corrosion factors such as those listed above and are subject to severe corrosive conditions. Furthermore, it is desirable to recycle the removed heavy metals as raw materials for non-ferrous smelting.
[0011] The present invention has been made in consideration of the above circumstances, and aims to provide a method for producing a corrosion inhibitor for a boiler, which can efficiently remove corrosion factors that corrode a boiler and impurities that do not contribute to the synthesis of the corrosion inhibitor, and which can reduce the amounts of Si source and Al source added in the synthesis of the corrosion inhibitor, and a boiler and a method for inhibiting corrosion of the boiler. Another aim is to recycle the removed heavy metals as raw materials for non-ferrous smelting. [Means for solving the problem]
[0012] In order to solve the above problems, the present invention proposes the following means. (1) The method for producing a corrosion inhibitor for a boiler of the present invention comprises the steps of: (a) adding a first corrosion inhibitor for a boiler to combustion ash generated at a first waste treatment facility; The combustion ash contains Ca, Al and Si. and washing the combustion ash obtained in the obtaining step. and A cleaning process for pickling, and a water washing process in the cleaning process. and Acid-washed combustion ash Then, alkaline hydrothermal treatment is performed. A manufacturing process for obtaining a second boiler corrosion inhibitor. When the content of Ca contained in the combustion ash to be subjected to the alkaline hydrothermal treatment exceeds 16% by mass, the Ca content is adjusted to 16% by mass or less, and when the total content of Si and Al contained in the combustion ash to be subjected to the alkaline hydrothermal treatment is less than 11% by mass, a Si source or an Al source is added during the alkaline hydrothermal treatment so that the total content of Si and Al becomes 11% by mass or more. It is characterized by the above.
[0013] According to the present invention, it is possible to efficiently remove corrosion factors that corrode boilers and impurities that do not contribute to the synthesis of a corrosion inhibitor, and to reduce the amounts of Si source and Al source added in the synthesis of the corrosion inhibitor. Also, it is possible to obtain a corrosion inhibitor whose Ca content, Al content and Si content are within the ranges suitable for the synthesis of the corrosion inhibitor.
[0014] (2) In the method for producing the boiler corrosion inhibitor, the average particle diameter (d 50 ) is preferably 10 μm or more and 25 μm or less.
[0015] Average particle diameter (d 50 ) is 10 μm or more and 25 μm or less, the particle size is capable of exerting a corrosion inhibiting effect.
[0016] (3) In the method for producing a corrosion inhibitor for a boiler, the corrosion inhibitor for a boiler obtained in the production step preferably contains 40 mass % or more of amorphous matter.
[0017] The corrosion inhibitor exhibits a good corrosion inhibition effect due to the amorphous content of 40 mass %.
[0018] (4) In the method for producing a corrosion inhibitor for a boiler, it is preferable that the corrosion inhibitor for a boiler obtained in the production process contains, in addition to the amorphous phase, at least one or more selected from the group consisting of calcium phosphate, calcium carbonate, an aluminate phase, hercynite, zeolite, gehlenite, magnesioferrite, magnesium zinc iron ion oxide, calcium titanate, zinc oxide, and akermanite.
[0019] By including these components in addition to the amorphous phase, impurities can be efficiently removed, and a corrosion inhibitor can be obtained in which the Ca content, Al content, and Si content are within ranges suitable for the synthesis of the corrosion inhibitor.
[0020] (5) In the method for producing the corrosion inhibitor for a boiler, the second corrosion inhibitor for a boiler obtained in the production process is preferably obtained by subjecting combustion ash that has been washed with water or pickled in the cleaning process to an alkaline hydrothermal treatment.
[0021] (6) In the method for producing the corrosion inhibitor for a boiler, it is preferable that an alkaline aqueous solution is used in the production step, and the second corrosion inhibitor for a boiler is obtained by washing away the alkaline aqueous solution.
[0022] By using an alkaline aqueous solution to produce a precipitate and then washing it with water, excess substances adhering to the surface of the corrosion inhibitor can be removed, preventing the pores from becoming clogged, and a corrosion inhibitor for boilers with a high corrosion inhibition effect can be obtained.
[0023] (7) In the method for producing the boiler corrosion inhibitor, the second boiler corrosion inhibitor obtained in the production process has a BET specific surface area of 90 m 2 It is preferable that the molecular weight is 1 / g or more.
[0024] BET specific surface area is 90m 2 / g or more, the surface irregularities are large and corrosive substances can be adsorbed on the surface, thereby preventing the corrosive substances from reaching the superheating organ of the boiler.
[0025] (8) In the method for producing a corrosion inhibitor for a boiler, the cleaning step preferably includes an acid washing step of the combustion ash obtained in the obtaining step.
[0026] The acid washing process enables the heavy metals contained in the combustion ash to be eluted and removed.
[0027] (9) In the method for producing the boiler corrosion inhibitor, the BET specific surface area of the second boiler corrosion inhibitor obtained in the production process is 60 m 2 It is preferable that the molecular weight is 1 / g or more.
[0028] BET specific surface area is 60m 2 / g or more, the surface irregularities are large and corrosive substances can be adsorbed onto the surface, thereby preventing the corrosive substances from reaching the inner surface of the boiler (particularly the superheating organ).
[0029] (10) In the method for producing a corrosion inhibitor for a boiler, it is preferable that the first waste treatment facility is a melting furnace, the combustion ash is molten fly ash containing heavy metals, and the cleaning treatment step includes subjecting the combustion ash obtained in the obtaining step to an acid washing treatment.
[0030] The acid pickling process enables the heavy metals contained in the molten fly ash to be eluted and removed.
[0031] (11) In the method for producing a corrosion inhibitor for a boiler, it is preferable that Zn contained in the combustion ash pickled in the cleaning step is eluted by the pickling treatment.
[0032] It is estimated that the Zn content is higher in combustion ash generated at a waste treatment facility where a corrosion inhibitor for boilers is added than in combustion ash generated at a waste treatment facility where a corrosion inhibitor for boilers is not added, due to the amount of the corrosion inhibitor added. Therefore, by dissolving Zn from the latter combustion ash, it is possible to efficiently recover Zn from the combustion ash.
[0033] (12) In the method for producing a corrosion inhibitor for a boiler, it is preferable that the combustion ash that has been subjected to the pickling treatment in the cleaning treatment step is in a slurry state, and the pH of the combustion ash is 2.5 or more and 5.5 or less.
[0034] If the pH is less than 2.5, the elution rate of Si and Al, which are components of the corrosion inhibitor, increases. In addition, the viscosity of the slurry increases, making it difficult to separate the slurry into a liquid portion and the combustion ash after pickling treatment in the subsequent process. If the pH is 2.5 or higher, the elution rate of Si and Al is suppressed. Note that the higher the slurry pH, the lower the elution rate of Pb, Zn, and Cu, which are corrosion factors of boiler superheater tubes, but the corrosion inhibition effect is still sufficient.
[0035] (13) In the method for producing a corrosion inhibitor for a boiler, it is preferable that the first waste treatment facility is a stoker furnace, the combustion ash is incineration fly ash, and the washing treatment step includes washing the combustion ash obtained in the obtaining step with water.
[0036] The corrosion inhibitor according to the present invention is preferably applied to a stoker furnace as a waste treatment facility. Since the combustion ash is incineration fly ash, water-soluble compounds including Pb, Ca, Na and K contained in the incineration fly ash can be dissolved in water and separated. By removing these compounds, a corrosion inhibitor for boilers having a corrosion inhibitor effect on boilers can be produced with little effort.
[0037] (14) In the method for producing a corrosion inhibitor for a boiler, the cleaning treatment step is preferably performed once.
[0038] In the cleaning process performed in this embodiment, water-soluble compounds including at least one selected from the group consisting of Pb, Ca, Na, and K can be removed by dissolving them in a single cleaning process. Also, only one pickling process is required. In the prior art, for example, more than 10 pickling processes are required to dissolve an acid-soluble compound, but since only one pickling process is required, the pickling process can be simplified.
[0039] (15) In the manufacturing method of the boiler corrosion inhibitor, the first boiler corrosion inhibitor is preferably a boiler corrosion inhibitor obtained by subjecting combustion ash generated in the first waste treatment facility or combustion ash generated in a second waste treatment facility different from the first waste treatment facility to a water-washing treatment or an acid-washing treatment.
[0040] It is possible to provide a corrosion inhibitor from which the metal elements removed by the water washing treatment or the pickling treatment have been removed.
[0041] (16) In the method for producing the boiler corrosion inhibitor, it is preferable that in the obtaining step, the boiler corrosion inhibitor obtained in the producing step is used as the first boiler corrosion inhibitor, and the obtaining step, the cleaning treatment step, and the producing step are repeated.
[0042] The corrosion inhibitor can be reused by repeatedly treating the combustion ash recovered from the boiler.
[0043] (17) In the above-mentioned method for producing a corrosion inhibitor for a boiler, the second corrosion inhibitor for a boiler obtained in the above-mentioned production step preferably has a calcium carbonate content of 13 mass % or less.
[0044] By controlling the content of calcium carbonate to 13 mass % or less, it is possible to suppress a decrease in the corrosion inhibiting effect.
[0047] (1 8 ) The method for inhibiting corrosion in a boiler according to the present invention is a method for inhibiting corrosion in a superheating device provided in an exhaust gas passage through which the combustion exhaust gas of the boiler passes, and is characterized in that a corrosion inhibitor for boilers manufactured by the manufacturing method described in any one of (1) to (17) is supplied into the exhaust gas passage.
[0048] By supplying any one of the above-described corrosion inhibitors into an exhaust gas passage, corrosion of a superheating device provided in the exhaust gas passage through which combustion exhaust gas from a boiler passes can be suppressed. Effect of the Invention
[0049] According to the present invention, it is possible to provide a method for producing a corrosion inhibitor that can efficiently remove corrosion factors that corrode a boiler and impurities that do not contribute to the synthesis of a corrosion inhibitor, and that can reduce the amounts of a Si source and an Al source added in the synthesis of the corrosion inhibitor. [Brief description of the drawings]
[0050] [Figure 1] 1 is a flowchart showing a method for producing a corrosion inhibitor according to an embodiment of the present invention. [Diagram 2] 4 is a graph showing the elution rate of an acid-soluble component (Pb) eluted into a filtrate obtained by solid-liquid separation of a fourth slurry in Example 1. FIG. [Diagram 3] 4 is a graph showing the elution rate of an acid-soluble component (Zn) eluted into a filtrate obtained by solid-liquid separation of a fourth slurry in Example 1. FIG. [Figure 4] FIG. 2 is a graph showing the elution rate of an acid-soluble component (Cu) eluted into a filtrate obtained by solid-liquid separation of a fourth slurry in Example 1. [Diagram 5] FIG. 4 is a graph showing the elution rate of an acid-soluble component (Si) eluted into a filtrate obtained by solid-liquid separation of a fourth slurry in Example 1. [Figure 6] FIG. 2 is a graph showing the elution rate of an acid-soluble component (Ca) eluted into a filtrate obtained by solid-liquid separation of a fourth slurry in Example 1. [Figure 7] FIG. 4 is a graph showing the elution rate of an acid-soluble component (Al) eluted into a filtrate obtained by solid-liquid separation of a fourth slurry in Example 1. [Figure 8] FIG. 11 is a graph showing the elution rate of an acid-soluble component eluted in a filtrate obtained by solid-liquid separation of a fourth slurry in Example 4. [Figure 9] FIG. 1 is a diagram showing the weight loss rate of a boiler superheater tube at 550° C. in an example and a comparative example. [Figure 10] FIG. 2 is a graph showing the weight loss rate of a boiler superheater tube at 500° C. in an embodiment. [Figure 11] FIG. 2 is a diagram showing the results of EDS analysis of a cross section of a simulated superheater tube subjected to a corrosion test in Example 1. [Figure 12] FIG. 2 is a diagram showing the results of color mapping of Si in a cross section of a simulated superheater tube subjected to a corrosion test in Example 1, which was investigated by EDS analysis. [Figure 13] FIG. 2 is a diagram showing the results of color mapping of Al obtained by investigating the cross section of a simulated superheater tube subjected to a corrosion test by EDS analysis in Example 1. [Figure 14] FIG. 2 is a diagram showing the results of color mapping of Na, obtained by investigating the cross section of a simulated superheater tube subjected to a corrosion test by EDS analysis in Example 1. [Figure 15] FIG. 1 is a diagram showing the results of investigating a cross section of a simulated superheater tube subjected to a corrosion test by EDS analysis and color mapping K in Example 1. [Figure 16] FIG. 2 is a diagram showing the results of color mapping of Ca in a cross section of a simulated superheater tube subjected to a corrosion test in Example 1, which was investigated by EDS analysis. [Figure 17] FIG. 2 is a diagram showing the results of color mapping of Cl obtained by investigating the cross section of a simulated superheater tube subjected to a corrosion test by EDS analysis in Example 1. [Figure 18] FIG. 11 is a diagram showing the results of EDS analysis of a cross section of a simulated superheater tube subjected to a corrosion test in Example 5. [Figure 19] FIG. 13 is a diagram showing the results of color mapping of Cl obtained by investigating the cross section of a simulated superheater tube subjected to a corrosion test by EDS analysis in Example 5. [Figure 20] FIG. 13 is a diagram showing the results of color mapping of Si in a cross section of a simulated superheater tube subjected to a corrosion test in Example 5, which was investigated by EDS analysis. [Figure 21] FIG. 13 is a diagram showing the results of color mapping of Ca in a cross section of a simulated superheater tube subjected to a corrosion test, which was investigated by EDS analysis, in Example 5. [Figure 22]FIG. 13 is a diagram showing the results of investigating the cross section of a simulated superheater tube subjected to a corrosion test by EDS analysis and color mapping Pb in Example 5. [Diagram 23] FIG. 13 is a diagram showing the results of investigating the cross section of a simulated superheater tube subjected to a corrosion test by EDS analysis and color mapping K in Example 5. [Figure 24] FIG. 1 shows the results of an analysis of the components of corrosion products inside the corrosion product layer when simulated molten fly ash and a mixture of simulated molten fly ash and a corrosion inhibitor (Example 1) were applied to a simulated superheater tube and a corrosion test was carried out at 550°C for 100 hours. [Diagram 25] FIG. 1 shows the results of an analysis of the components of corrosion products near the interface between the base material (simulated superheater tube) and the corrosion product when a simulated molten fly ash and a mixture of the simulated molten fly ash and a corrosion inhibitor (Example 1) were applied to a simulated superheater tube and a corrosion test was carried out at 550°C for 100 hours. [Figure 26] FIG. 1 is a configuration diagram showing an example of a stoker furnace to which the corrosion inhibitor according to the present invention can be applied. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0051] [Method of manufacturing corrosion inhibitor] Hereinafter, an embodiment of a method for producing a corrosion inhibitor according to the present invention will be described with reference to Fig. 1. Fig. 1 is a flow chart showing the method for producing a corrosion inhibitor according to the embodiment of the present invention.
[0052] The method for producing a corrosion inhibitor according to the present embodiment is a method for producing a second corrosion inhibitor for a boiler from at least one of molten fly ash and incineration fly ash generated in a first waste treatment facility to which a first corrosion inhibitor for a boiler described later is added. In the following description, ash containing at least one of molten fly ash and incineration fly ash may be referred to as combustion ash. As shown in Fig. 1, the method for producing a corrosion inhibitor according to the present embodiment includes a first step (S1) of stirring and mixing a first slurry containing water and combustion ash, which is at least one of molten fly ash and incineration fly ash generated in a first waste treatment facility to which a first corrosion inhibitor for boilers is added, to dissolve water-soluble compounds, which contain at least one selected from the group consisting of Pb, Ca, Na, and K, contained in at least one of the molten fly ash and incineration fly ash, to prepare a second slurry. This first step can be called a water washing treatment.
[0053] In addition, a corrosion inhibitor produced by the manufacturing method of the present embodiment described in detail below from combustion ash generated in a waste treatment facility where a corrosion inhibitor for boilers is not added can be applied as the first corrosion inhibitor for boilers. In addition, a corrosion inhibitor for boilers produced by the manufacturing method of the present embodiment described in detail below from combustion ash generated in a waste treatment facility where a corrosion inhibitor for boilers produced by the manufacturing method of the present embodiment described in detail below can be used as the first corrosion inhibitor for boilers. In addition, a corrosion inhibitor produced by the manufacturing method of the present embodiment described in detail below from combustion ash generated in a waste treatment facility operated using a corrosion inhibitor for boilers such as natural zeolite can be used as the first corrosion inhibitor for boilers.
[0054] The method for producing a corrosion inhibitor according to this embodiment includes a second step (S2) of separating the second slurry into a liquid fraction and combustion ash, which is at least one of molten fly ash and incineration fly ash after water washing treatment.
[0055] The method for producing a corrosion inhibitor according to the present embodiment includes a third step (S3) of adding hydrochloric acid or nitric acid to a third slurry containing combustion ash, which is at least one of the molten fly ash and the incineration fly ash after the water washing treatment, and water, while stirring and mixing the third slurry, thereby dissolving an acid-soluble compound containing at least one selected from the group consisting of Ca, Pb, and Cu contained in at least one of the molten fly ash and the incineration fly ash after the water washing treatment, to prepare a fourth slurry. This third step can be called an acid washing treatment. In addition, one or both of the water washing treatment and the acid washing treatment can be called a cleaning treatment step. The method for producing a corrosion inhibitor according to this embodiment includes a fourth step (S4) of separating the fourth slurry into a liquid fraction and combustion ash, which is at least one of molten fly ash after pickling treatment and incineration fly ash. The method for producing a corrosion inhibitor according to this embodiment includes a fifth step (S5) of synthesizing a corrosion inhibitor by performing an alkaline hydrothermal treatment in which a fifth slurry containing combustion ash, which is at least one of molten fly ash after pickling treatment and incineration fly ash, and an alkaline aqueous solution is heated, stirred, and mixed to synthesize a corrosion inhibitor. The method for producing a corrosion inhibitor according to this embodiment includes a sixth step (S6) of separating the fifth slurry from the fifth step (S5) into a liquid portion (e.g., a filtrate) and a corrosion inhibitor to obtain the corrosion inhibitor.
[0056] The corrosion inhibitor obtained in this embodiment contains, for example, 40 mass% or more of amorphous material containing at least one of CSH (calcium silicate hydrate) and CASH (calcium aluminosilicate hydrate), or not containing these, or an amorphous material combining both of these amorphous materials as a major component, and contains at least one or more types selected from the group consisting of calcium phosphate, calcium carbonate, aluminate phase, hercynite, zeolite, gehlenite, magnesioferrite, magnesium zinc iron ion oxide, calcium titanate, zinc oxide, and akermanite.
[0057] (First step (S1)) The first step (S1) is a step of stirring and mixing a first slurry containing combustion ash, which is at least one of molten fly ash and incineration fly ash, and water, to elute water-soluble compounds, which are contained in at least one of the molten fly ash and incineration fly ash and contain at least one selected from the group consisting of Pb, Ca, Na, and K. That is, the first step (S1) is a step of eluting water-soluble compounds, which are contained in the molten fly ash, incineration fly ash, or a mixture of the molten fly ash and incineration fly ash and contain at least one selected from the group consisting of Pb, Ca, Na, and K.
[0058] In the first step (S1), combustion ash, which is at least one of molten fly ash and incineration fly ash, is added to water to prepare a first slurry. Molten fly ash is soot and dust generated when waste is melted in a gasification melting furnace or an ash melting furnace, and contains elements such as lead (Pb), calcium (Ca), sodium (Na), potassium (K), copper (Cu), and zinc (Zn). In detail, molten fly ash contains water-soluble compounds containing at least one selected from the group consisting of Pb, Ca, Na, and K, and acid-soluble compounds. Examples of water-soluble compounds include sodium chloride (NaCl), potassium chloride (KCl), calcium chloride (CaCl), and calcium chloride (CaCl). 2 ), calcium hydroxide (Ca(OH) 2 ), lead(II) chloride (PbCl 2 ) and the like. Compounds that are soluble in acid include copper(II) oxide (CuO), zinc oxide (ZnO), lead metasilicate (PbSiO 3 The Ca content of the molten fly ash is in the range of 15% by mass to 25% by mass, the Si content is in the range of 2.5% by mass to 6.0% by mass, the Al content is in the range of 0.5% by mass to 4% by mass, the Pb content is in the range of 0.3% by mass to 3% by mass, the Zn content is in the range of 1.0% by mass to 6.0% by mass, the Cu content is in the range of 0.0% by mass to 0.5% by mass, and the Cl content is in the range of 10% by mass to 25% by mass. In the method for producing a corrosion inhibitor according to the present embodiment, it is particularly preferable to use, as the molten fly ash, fly ash generated from a waste treatment facility where waste is treated by high-temperature melting.
[0059] Incineration fly ash is soot generated when waste is burned in a stoker furnace, a fluidized bed furnace, a rotary kiln furnace, etc., and contains elements such as lead (Pb), calcium (Ca), sodium (Na), potassium (K), copper (Cu), and zinc (Zn). In detail, incineration fly ash contains water-soluble compounds containing at least one selected from the group consisting of Pb, Ca, Na, and K, and acid-soluble compounds. Examples of water-soluble compounds include sodium chloride (NaCl), potassium chloride (KCl), calcium chloride (CaCl), and calcium chloride (CaCl). 2 ), calcium hydroxide (Ca(OH) 2), lead(II) chloride (PbCl 2 ) and the like. Compounds that are soluble in acid include copper(II) oxide (CuO), zinc oxide (ZnO), lead metasilicate (PbSiO 3 The Ca content of the incineration fly ash is in the range of 15% by mass to 25% by mass, the Si content is in the range of 2.5% by mass to 6.0% by mass, the Al content is in the range of 0.5% by mass to 4% by mass, the Pb content is in the range of 0.3% by mass to 3% by mass, the Zn content is in the range of 1.0% by mass to 6.0% by mass, the Cu content is in the range of 0.0% by mass to 0.5% by mass, and the Cl content is in the range of 10% by mass to 25% by mass. In the method for producing a corrosion inhibitor according to the present embodiment, it is particularly preferable to use incineration fly ash generated from a waste treatment facility where waste is completely combusted at high temperatures. In addition, in the mixture of molten fly ash and incineration fly ash, the Ca content is in the range of 15 mass% or more and 25 mass% or less, the Si content is in the range of 2.5 mass% or more and 6.0 mass% or less, the Al content is in the range of 0.5 mass% or more and 4 mass% or less, the Pb content is in the range of 0.3 mass% or more and 3 mass% or less, the Zn content is in the range of 1.0 mass% or more and 6.0 mass% or less, the Cu content is in the range of 0.0 mass% or more and 0.5 mass% or less, and the Cl content is in the range of 10 mass% or more and 25 mass% or less.
[0060] In the first slurry, the ratio of combustion ash, which is at least one of molten fly ash and incineration fly ash, to water (molten fly ash / water) is preferably 1 / 20 or more and 1 / 5 or less, and more preferably 1 / 10 or more and 1 / 5 or less, in mass ratio.
[0061] Examples of water that can be used include tap water and industrial water.
[0062] The first slurry is then stirred and mixed. The method for stirring and mixing the first slurry is not particularly limited, but examples include a method of stirring using stirring blades such as inclined battle blades or turbine blades, a method of placing at least two baffle plates facing each other in a reaction vessel and stirring using stirring blades, etc.
[0063] The rotation speed of the stirring blades or the like when stirring the first slurry is not particularly limited as long as the molten fly ash and the incineration fly ash do not remain at the bottom of the reaction vessel. For example, the rotation speed is preferably 200 rpm or more and 400 rpm or less, and more preferably 250 rpm or more and 350 rpm or less. If the rotation speed of the impeller or the like when stirring the first slurry is 400 rpm or more, the molten fly ash and the incineration fly ash will not remain at the bottom of the reaction vessel, but since the power required for stirring increases with increasing rotation speed, it is preferable to keep the rotation speed as low as possible. On the other hand, if the rotation speed of the impeller or the like when stirring the first slurry is 200 rpm or less, the molten fly ash and the incineration fly ash will remain at the bottom of the reaction vessel, and the elution of water-soluble compounds will decrease.
[0064] The temperature at which the first slurry is stirred and mixed is preferably 5°C or higher and 50°C or lower, and more preferably 10°C or higher and 35°C or lower.
[0065] The time for stirring and mixing the first slurry is preferably from 10 minutes to 60 minutes, more preferably 30 minutes or less, more preferably 20 minutes or less, and most preferably 10 minutes or less. Even if the time for stirring and mixing the first slurry is 60 minutes or more, the dissolution rate of the water-soluble compounds does not change significantly (converges). On the other hand, if the time for stirring and mixing the first slurry is 10 minutes or less, the dissolution rate of the water-soluble compounds does not converge.
[0066] The first slurry is stirred and mixed once.
[0067] In this manner, in the first step (S1), a first slurry containing combustion ash, which is at least one of molten fly ash and incineration fly ash, and water is stirred and mixed to dissolve water-soluble compounds, which include at least one selected from the group consisting of Pb, Ca, Na, and K, contained in at least one of the molten fly ash and incineration fly ash, to prepare a second slurry. The obtained second slurry contains water, combustion ash, which is at least one of molten fly ash and incineration fly ash dispersed in water, and sodium chloride (NaCl), potassium chloride (KCl), calcium chloride (CaCl), etc. dissolved in water. 2 ), calcium hydroxide (Ca(OH) 2 ), lead(II) chloride (PbCl 2 ) and water-soluble compounds such as
[0068] In the first step (S1), as a method for confirming that the water-soluble compounds have been separated from the molten fly ash, for example, ICP emission spectrometry, ion chromatography, or an analysis method using a detector tube is used.
[0069] (Second step (S2)) The second step (S2) is a step of separating the second slurry obtained in the first step (S1) into a liquid fraction (e.g., filtrate) and combustion ash, which is at least one of molten fly ash and incineration fly ash after water washing treatment. The combustion ash, which is at least one of the molten fly ash and the incineration fly ash after the water washing treatment, refers to at least one of the molten fly ash and the incineration fly ash that has been subjected to a treatment in the first step (S1) of stirring and mixing the first slurry to elute water-soluble compounds, which include at least one selected from the group consisting of Pb, Ca, Na, and K, contained in the combustion ash, which is at least one of the molten fly ash and the incineration fly ash.
[0070] The method for separating the liquid fraction from the combustion ash, which is at least one of the molten fly ash and the incineration fly ash after the water washing treatment, is not particularly limited, but for example, solid-liquid separation using a cake filtering device (roller press, filter press, screw press, etc.), centrifugal separation, multiple disk rotary dehydration, multiple vibration filter, etc. may be used.
[0071] In addition, after the liquid and the water washing treatment, the combustion ash, which is either the molten fly ash or the incineration fly ash, is separated by solid-liquid separation using a cake filtering device (roller press, filter press, screw press, etc.), centrifugal separation, multiple disk rotary dehydration, multiple vibration filter, etc., and then, water is dropped onto the combustion ash, which is either the molten fly ash or the incineration fly ash, to remove sodium chloride (NaCl), potassium chloride (KCl), calcium chloride (CaCl), etc., remaining on the surface of either the molten fly ash or the incineration fly ash. 2 ), calcium hydroxide (Ca(OH) 2 ), lead(II) chloride (PbCl 2 ) and other water-soluble compounds may be washed away.
[0072] (Third step (S3)) The third step (S3) is a step of adding hydrochloric acid or nitric acid to a third slurry containing combustion ash, which is at least one of the molten fly ash and the incineration fly ash after the water-washing treatment, and water, while stirring and mixing the third slurry, to dissolve an acid-soluble compound, which contains at least one selected from the group consisting of Pb, Zn, and Cu, contained in the combustion ash, which is at least one of the molten fly ash and the incineration fly ash after the water-washing treatment.
[0073] In the third step (S3), first, combustion ash, which is at least one of the molten fly ash and the incineration fly ash after the water washing treatment, is added to water to prepare a third slurry.
[0074] Next, hydrochloric acid (HCl) or nitric acid (HNO 3 In this case, the pH of the third slurry is preferably 2.5 to 5.5, more preferably 2.5 to 4.5, and even more preferably 2.5 to 4.0. That is, hydrochloric acid (HCl) or nitric acid (HNO 3 The pH of the third slurry is measured using a pH measuring device such as a pH meter. If the pH of the third slurry is less than 2.5, the elution rate of heavy metals such as Pb, Zn, and Cu, which are corrosion factors of boiler superheater tubes, and the elution rate of Ca, which is an inhibitor when synthesizing a corrosion inhibitor, will increase, but the elution rate of Si and Al, which are components of the corrosion inhibitor, will also increase, which is not preferable. In addition, since the viscosity of the third slurry increases, it becomes difficult to separate the fourth slurry into at least one of the liquid portion and the molten fly ash and the incineration fly ash after the pickling treatment in the fourth step (S4). On the other hand, if the pH of the third slurry is 2.5 or more, and particularly if the pH of the third slurry is 3.5 to 5.5, the elution rate of Si and Al is suppressed, which is preferable. It has been confirmed that the higher the pH of the third slurry, the lower the elution rate of Pb, Zn, and Cu, which are corrosion factors of boiler superheater tubes, but the corrosion inhibition effect can be obtained.
[0075] Examples of water that can be used include tap water and industrial water.
[0076] Available hydrochloric acid (HCl) and nitric acid (HNO 3 Examples of the acid salt include hydrochloric acid, concentrated hydrochloric acid, and nitric acid. The concentrations of hydrochloric acid and concentrated hydrochloric acid are about 0.5N (mol / L) to 12.0N (mol / L), and the concentrations of nitric acid and concentrated nitric acid are about 0.1N (mol / L) to 10N (mol / L), but any concentration may be used.
[0077] In the third slurry, the ratio of at least one of the molten fly ash and the incineration fly ash to the liquid content (total of water and hydrochloric acid or nitric acid) (molten fly ash / liquid content) is preferably 1 / 20 or more and 1 / 5 or less, more preferably 1 / 10 or more and 1 / 5 or less, in mass ratio.
[0078] A third slurry containing hydrochloric acid or nitric acid is then stirred and mixed. The method for stirring and mixing the third slurry containing hydrochloric acid or nitric acid is not particularly limited, but examples include stirring with an inclined battle blade, turbine blade, or other stirring blade, and stirring with stirring blades by arranging at least two baffle plates facing each other in a reaction vessel.
[0079] The rotation speed of the stirring blades or the like when stirring the third slurry containing hydrochloric acid or nitric acid is not particularly limited, but is preferably, for example, 200 rpm or more and 400 rpm or less, and more preferably 250 rpm or more and 350 rpm or less. If the rotation speed of the impeller or the like when stirring the third slurry containing hydrochloric acid or nitric acid is 400 rpm or more, the molten fly ash or the like will not remain at the bottom of the reaction vessel, but since the power required for stirring increases with increasing rotation speed, it is preferable that the rotation speed be as small as possible. On the other hand, if the rotation speed of the impeller or the like when stirring the third slurry containing hydrochloric acid or nitric acid is 200 rpm or less, the compounds will remain at the bottom of the reaction vessel, and the elution of water-soluble compounds will decrease.
[0080] The temperature at which the third slurry containing hydrochloric acid or nitric acid is stirred and mixed is preferably 20°C or higher and 80°C or lower, and more preferably 20°C or higher and 50°C or lower.
[0081] The time for stirring and mixing the third slurry containing hydrochloric acid or nitric acid is preferably 10 minutes or more and 60 minutes or less after the third slurry pH reaches the predetermined pH. Even if the third slurry containing hydrochloric acid or nitric acid is stirred and mixed for 60 minutes or more, the dissolution of the acid-soluble compounds is almost complete. On the other hand, if the third slurry containing hydrochloric acid or nitric acid is stirred and mixed for 10 minutes or less, the reaction between the acid-soluble compounds and the acid may not proceed sufficiently.
[0082] The third slurry containing hydrochloric acid or nitric acid is stirred and mixed once.
[0083] In this manner, in the third step (S3), the third slurry containing the combustion ash, which is at least one of the molten fly ash and the incineration fly ash after the water-washing treatment, water, and an acid (hydrochloric acid or nitric acid) is stirred and mixed to dissolve the acid-soluble compound, which is at least one selected from the group consisting of Pb, Zn, and Cu, contained in the at least one of the molten fly ash and the incineration fly ash after the water-washing treatment, to prepare a fourth slurry. The obtained fourth slurry is a mixture of water containing hydrochloric acid or nitric acid, combustion ash, which is at least one of the molten fly ash and the incineration fly ash dispersed in the water, and copper oxide (II) (CuO), zinc oxide (ZnO), lead metasilicate (PbSiO ), which are dissolved in the water containing hydrochloric acid or nitric acid. 3 ) and acid-soluble compounds such as
[0084] In the third step (S3), as a method for confirming that the acid-soluble compounds have been separated from the combustion ash, which is at least one of the molten fly ash and the incineration fly ash after the water washing treatment, for example, a method is used in which the concentrations of Pb, Zn, Cu, Ca, Si, and Al dissolved in the liquid obtained in the fourth step are analyzed by ICP emission spectrometry, a detector tube, etc. Alternatively, a method is used in which the concentrations of Pb, Zn, Cu, Ca, Si, and Al contained in the combustion ash, which is at least one of the molten fly ash and the incineration fly ash after the acid washing treatment obtained in the fourth step, are measured by X-ray fluorescence analysis, energy dispersive analysis (EDS), or ICP emission spectrometry after wet dissolution.
[0085] (Fourth step (S4)) The fourth step (S4) is a step of separating the fourth slurry obtained in the third step (S3) into a liquid fraction (e.g., filtrate) and combustion ash, which is at least one of the molten fly ash and the incineration fly ash after the pickling treatment. The combustion ash, which is at least one of the molten fly ash and the incineration fly ash after the acid washing treatment, refers to the combustion ash, which is at least one of the molten fly ash and the incineration fly ash, which is subjected to a treatment in the third step (S3) in which a third slurry containing hydrochloric acid or nitric acid is added is stirred and mixed to elute an acid-soluble compound containing at least one selected from the group consisting of Pb, Zn, and Cu contained in the combustion ash, which is at least one of the molten fly ash and the incineration fly ash after the water washing treatment.
[0086] The method for separating the liquid fraction from the combustion ash, which is at least one of the molten fly ash and the incineration fly ash after the water washing treatment, is not particularly limited, but for example, solid-liquid separation using a cake filtering device (roller press, filter press, screw press), centrifugal separation, multiple disk rotary dehydration, multiple vibration filter, etc. may be used.
[0087] In addition, the liquid and the combustion ash, which is at least one of the molten fly ash and the incineration fly ash after the acid washing treatment, may be subjected to solid-liquid separation using a cake filtering device (roller press, filter press, screw press), centrifugal separation, multiple disk rotary dehydration, multiple vibration filter, or the like, and then water may be dropped onto at least one of the molten fly ash and the incineration fly ash to wash away the acid remaining on the surface of the combustion ash, which is at least one of the molten fly ash and the incineration fly ash. At least one of the molten fly ash and the incineration fly ash obtained after pickling treatment as described above may be used as a corrosion inhibitor.
[0088] (Fifth step (S5)) The fifth step (S5) is a step of synthesizing a corrosion inhibitor by heating and stirring a fifth slurry containing combustion ash, which is at least one of the molten fly ash and the incineration fly ash after the pickling treatment, and an alkaline aqueous solution.
[0089] In the fifth step (S5), first, combustion ash, which is at least one of molten fly ash after pickling treatment and incineration fly ash, is added to an alkaline aqueous solution to prepare a fifth slurry.
[0090] Examples of the alkaline aqueous solution include sodium hydroxide (NaOH) aqueous solution and calcium hydroxide (Ca(OH) 2 aqueous solution, potassium hydroxide (KOH) aqueous solution, sodium carbonate (NaCO 2 ) aqueous solution, sodium bicarbonate (NaHCO 3 In addition, by using the alkaline effluent discharged in the second step, calcium ions in the effluent can be effectively utilized. The concentration of the alkaline aqueous solution is preferably 1N or more and 4N or less. If the concentration of the alkaline aqueous solution is too low, the elution of reactive components from the combustion ash, which is at least one of the molten fly ash and the incineration fly ash, is delayed, making it difficult to produce the corrosion inhibitor. Conversely, if the concentration is too high, the gel network structure becomes too strong, which excessively restricts the movement of each ion within the gel, making it difficult for the reaction to produce the corrosion inhibitor to occur.
[0091] In the fifth slurry, the ratio of combustion ash, which is at least one of molten fly ash after pickling treatment and incineration fly ash, to the alkaline aqueous solution (combustion ash / alkaline aqueous solution) is preferably 1 / 2 or more and 1 / 5 or less in mass ratio.
[0092] Next, the fifth slurry is heated and stirred and mixed to perform an alkaline hydrothermal treatment, thereby synthesizing a corrosion inhibitor containing 40 mass% or more of amorphous matter as a main component, which may be amorphous matter containing at least one of CSH (calcium silicate hydrate) and CASH (calcium aluminosilicate hydrate), amorphous matter not containing these, or amorphous matter containing both of these amorphous matter together, and further containing at least one or more kinds selected from the group consisting of calcium phosphate, calcium carbonate, aluminate phase, hercynite, zeolite, gehlenite, magnesioferrite, magnesium zinc iron ion oxide, calcium titanate, zinc oxide, and akermanite. The method for stirring and mixing the fifth slurry is not particularly limited, but examples include stirring using stirring blades such as inclined battle blades and turbine blades, and stirring using stirring blades by placing at least two baffle plates opposite each other in a reaction vessel.
[0093] The rotation speed of the stirring blades or the like when stirring the fifth slurry is not particularly limited, but is preferably, for example, 200 rpm or more and 400 rpm or less, and more preferably 250 rpm or more and 350 rpm or less. If the rotation speed of the impeller or the like when stirring the fifth slurry is 200 rpm or more, the molten fly ash will not remain at the bottom of the reaction vessel, but since the power required for stirring increases as the rotation speed increases, it is preferable that the rotation speed is as small as possible. On the other hand, if the rotation speed of the impeller or the like when stirring the fifth slurry is 200 rpm or less, the molten fly ash will remain at the bottom of the reaction vessel, reducing the contact rate of the combustion ash, which is at least one of the molten fly ash and the incineration fly ash contained in the fifth slurry, with the alkaline aqueous solution, thereby inhibiting the production of the corrosion inhibitor.
[0094] The fifth slurry is stirred and mixed for preferably 1 hour or more, and more preferably 3 hours or more.
[0095] The fifth slurry is stirred and mixed once.
[0096] In the fifth step (S5), a Si source and an Al source are added to the fifth slurry so that the Ca content in the final corrosion inhibitor is 16 mass% or less, the ratio of Si to Al (Si / Al) is 1.2 or more by mass, and the total content of Si and Al is 11 mass% or more. This makes it possible to form a corrosion inhibitor while suppressing the inhibition of calcium carbonate production by Ca and the reduction in the corrosion inhibitory effect.
[0097] In a fifth step (S5), when the ratio of Si to Al (Si / Al) in the combustion ash, which is at least one of the molten fly ash and the incineration fly ash after the pickling treatment recovered in the fourth step (S4), is less than 1.2 in mass ratio and the total content of Si and Al is less than 11 mass%, a Si source and an Al source are added to the fifth slurry.
[0098] In the fifth step (S5), the Ca content, the Al content, and the Si content in the combustion ash, which is at least one of the molten fly ash and the incineration fly ash after the pickling treatment recovered in the fourth step (S4), can be confirmed using, for example, an X-ray fluorescence analyzer, an energy dispersive X-ray analyzer, an ICP emission spectrometer, or the like.
[0099] Common sources of silicon include silica sand, silicate glass, silicon-containing fly ash, molten slag, and steel slag, but also include sodium metasilicate and sodium orthosilicate. As the Al source, for example, sodium aluminate is generally used, but examples thereof include aluminum hydroxide, aluminum chloride, fly ash containing Al, molten slag, and steel slag.
[0100] (Sixth step (S6)) The sixth step (S6) is a step of separating the fifth slurry from the fifth step (S5) into a liquid fraction (eg, filtrate) and a corrosion inhibitor.
[0101] The method for separating the liquid component and the corrosion inhibitor is not particularly limited, but for example, solid-liquid separation using a cake filtering device (roller press, filter press, screw press, etc.), centrifugation, multiple disk rotary dehydration, multiple vibration filter, etc. may be used.
[0102] In addition, the recovered corrosion inhibitor may be subjected to solid-liquid separation using a cake filtering device (roller press, filter press, screw press, etc.), centrifugation, multiple disk rotary dehydration, multiple vibration filter, etc., and then water may be dropped onto the corrosion inhibitor to wash away the alkaline aqueous solution remaining on the surface of the corrosion inhibitor molten fly ash.
[0103] As described above, the second corrosion inhibitor for a boiler is obtained through the first step (S1) to the sixth step (S6). The obtained second boiler corrosion inhibitor contains 40 mass% or more of amorphous material containing at least one of CSH (calcium silicate hydrate) and CASH (calcium aluminosilicate hydrate), or not containing these, or amorphous material combining both of these amorphous materials as a major component, and further contains at least one or more types selected from the group consisting of calcium phosphate, calcium carbonate, aluminate phase, hercynite, zeolite, gehlenite, magnesioferrite, magnesium zinc iron ion oxide, calcium titanate, zinc oxide, and akermanite. In addition, the corrosion inhibitor may have an average particle size (d 50 The median diameter is 10 μm or more and 25 μm or less, and the BET specific surface area is 30 to 140 m 2 / g, which is large. Therefore, when supplied to the exhaust gas passage of a boiler, HCl, SO 2 When the corrosion inhibitor that has adsorbed the corrosive gas and the corrosion inhibitor that has not adsorbed the corrosive gas adhere to the surface of the corrosion layer formed on the metal interface or the outer surface of the superheater tube, the Cl generated by corrosion is released. 2 and PbCl 2 , ZnCl 2 , CuCl 2 By capturing low-melting-point molten salts including NaCl and KCl, corrosion inhibition effects can be achieved. The average particle size of the corrosion inhibitor (d 50 The median diameter is 10 μm or more and 25 μm or less, which is relatively large, but the BET specific surface area is 30 to 140 m 2 / g. Therefore, the above-mentioned corrosion inhibitor has excellent adsorption ability of corrosive substances, and has the effect of preventing corrosive substances from reaching the overheated organ. For the above reasons, it is desirable to have a large BET specific surface area. For example, 2 / g or more, and 2 It is more preferable that the molecular weight is 1 / g or more.
[0104] In addition, the main component amorphous in this embodiment may contain amorphous materials that do not contain CSH bonds or CASH bonds, such as CSH (calcium silicate hydrate) and CASH (calcium aluminosilicate hydrate). The amorphous materials may contain at least one element contained in combustion ash as an amorphous component. In any case, the corrosion inhibitor of the present embodiment preferably contains 40 mass % or more of amorphous matter. The presence of both of these amorphous matters can be confirmed by quantitative analysis using powder X-ray diffraction (XRD).
[0105] According to the hydrothermal treatment carried out in the fifth step in the manufacturing method of this embodiment, amorphous matter precipitates on the surfaces of the combustion ash particles, increasing the particle size. Furthermore, since the precipitated amorphous matter is in the form of small crystals, the specific surface area of the particles increases, and as a result, a corrosion inhibitor capable of adsorbing corrosive gases can be obtained. In addition, during the alkaline hydrothermal treatment, substances mainly composed of amorphous materials, including CSH and CASH, are generated on the surfaces of the combustion ash particles, so that the average particle size of the corrosion inhibitor produced by the production method of this embodiment increases. During the alkaline hydrothermal treatment, the amorphous particles generated on the surface of the combustion ash particles are small (several μm, for example, smaller than zeolite). As a result, the specific surface area of the corrosion inhibitor becomes large, allowing it to efficiently absorb corrosive gases. According to the manufacturing method of this embodiment, it is presumed that components of the combustion ash dissolve during the alkaline hydrothermal treatment, and amorphous matter precipitates on the surface of the silica or alumina.
[0106] The corrosion inhibitor has a ratio of Si to Al (Si / Al) of 1.2 or more by mass, and a total content of Si and Al of 11% by mass or more. The corrosion inhibitor has an average particle size of 10 μm or more and 25 μm or less. The average particle size of the corrosion inhibitor is measured by a laser diffraction particle size distribution measuring device, a capillary flow porosimeter, a mercury intrusion porosimeter, or the like.
[0107] (Seventh step (S7)) The method for producing a corrosion inhibitor according to the present embodiment may also include a seventh step (S7) of adding an alkaline aqueous solution to the liquid fraction (filtrate) separated in the fourth step (S4). This liquid contains copper(II) oxide (CuO), zinc oxide (ZnO), lead metasilicate (PbSiO 3 ) is an aqueous solution containing an acid-soluble compound.
[0108] Examples of the alkaline aqueous solution include sodium hydroxide (NaOH) aqueous solution and calcium hydroxide (Ca(OH) 2 In addition, by using the alkaline effluent discharged in the second step, calcium ions in the effluent can be effectively utilized. The concentration of the alkaline aqueous solution is not particularly limited.
[0109] In the seventh step (S7), an alkaline aqueous solution is added to the liquid fraction separated in the fourth step (S4) to adjust the pH of the liquid fraction to preferably 9.0 to 10.5, more preferably 9.5 to 10.0. The pH of the liquid fraction is measured using a pH measuring device such as a pH meter. If the pH of the liquid is 9.0 or higher, the Pb, Zn, and Cu contained in the liquid separated in the fourth step (S4) react with the alkaline aqueous solution to form a precipitate. On the other hand, if the pH of the liquid is 9.0 or lower or 10.5 or higher, a precipitate will form, but the heavy metal content in the precipitate will decrease.
[0110] By adding an alkaline aqueous solution to the liquid fraction separated in the fourth step (S4) in this way, at least one hydroxide selected from the group consisting of Pb, Zn, and Cu can be precipitated and the precipitate can be collected. In addition, the waste liquid after the precipitate collection can be effectively used as the water to be added in the first step.
[0111] As described above, according to the second manufacturing method for a corrosion inhibitor according to the present embodiment, it is possible to efficiently remove corrosion factors that corrode boilers and impurities (Pb, Ca, Na, K, Zn, Cu) that do not contribute to the synthesis of the corrosion inhibitor, and it is possible to obtain a corrosion inhibitor that allows the amounts of Si source and Al source to be reduced in the synthesis of the corrosion inhibitor. Furthermore, in the manufacturing method for the second corrosion inhibitor according to this embodiment, by adding a Si source and an Al source to the fifth slurry in the fifth step so that the ratio of Si to Al (Si / Al) in the corrosion inhibitor is 1.2 or more by mass and the total content of Si and Al is 11 mass% or more, it is possible to obtain a second corrosion inhibitor having a Ca content, an Al content and a Si content in a suitable range.
[0112] The second corrosion inhibitor obtained by the manufacturing method of the second corrosion inhibitor according to this embodiment can be supplied into an exhaust gas passage through which exhaust gas passes, thereby suppressing corrosion of the boiler of a waste treatment facility, in particular the boiler superheater tubes.
[0113] The second corrosion inhibitor according to the present embodiment is capable of suppressing HCl, SO 2 The corrosion inhibitor adsorbs corrosive gases such as HCl, and the corrosion inhibitor that has adsorbed the corrosive gas and the corrosion inhibitor that has not adsorbed the corrosive gas are attached to the superheater tube, and then the Cl generated by corrosion is 2 and PbCl 2 , ZnCl 2 , CuCl 2 This traps low-melting-point molten salts, including NaCl and KCl, thereby inhibiting the dissolution of oxide scale by the molten salts. Furthermore, by suppressing the chlorination reaction that accelerates the corrosion of the superheater tube, corrosion products mainly composed of oxides that have a corrosion-inhibiting effect can be formed, thereby suppressing the corrosion of the superheater tube.
[0114] As an example, a boiler to which the second corrosion inhibitor according to the present embodiment is applied includes a combustion furnace 2 for burning fuel, an exhaust gas passage 3 through which the combustion exhaust gas generated in the combustion furnace 2 passes, a superheater 5 having a superheating device 4 arranged in the exhaust gas passage 3, corrosion inhibitor supply devices 6, 7, and 8, and a control device (not shown). The boiler 1 can generate high-temperature, high-pressure superheated steam by superheating steam passing through the superheating device 4 with the heat of the combustion exhaust gas generated by the combustion of the fuel. The high-temperature, high-pressure superheated steam generated in the boiler 1 is used to rotate the turbine of a generator (not shown).
[0115] The boiler 1 is provided with corrosion inhibitor supply devices 6, 7, and 8 for suppressing corrosion of the superheating organ 4. The corrosion inhibitor supply device 6 is provided at a position where the second corrosion inhibitor is supplied into the exhaust gas passage 3 (particularly preferably into the second flue 21 upstream of the superheating organ 4). The corrosion inhibitor supply device 7 is provided at a position where the corrosion inhibitor can be supplied to the flue on the front side of the superheating organ 4. The corrosion inhibitor supply device 8 is provided at a position where the corrosion inhibitor can be supplied to the main combustion chamber 14 described later. The corrosion inhibitor supply devices 6, 7, and 8 may be various devices for supplying corrosion inhibitors. When the second corrosion inhibitor is in a particulate form, the corrosion inhibitor supply device is a particle supply device, and when the corrosion inhibitor is in a slurry form, the corrosion inhibitor supply device is a slurry supply device.
[0116] The boiler 1 shown in Fig. 26 is an example of a waste heat recovery boiler, and is equipped with a combustion furnace 2 for incinerating waste, and the combustion furnace 2 is equipped with a hopper 12 for supplying waste. The hopper 12 is connected to a main combustion chamber 14 via a chute 13. The waste supplied from the hopper 12 is sent to the main combustion chamber 14 through the chute 13. The main combustion chamber 14 is provided with a drying stoker 15, a combustion stoker 16, and a post-combustion stoker 17. Primary air is sent into the main combustion chamber 14 from below each of the stokers 15, 16, and 17, and secondary air is sent into the main combustion chamber 14 from the ceiling 14a of the main combustion chamber 14.
[0117] The waste thrown into the main combustion chamber 14 is first sent to the drying stoker 15, where it is dried and ignited by the primary air and the radiant heat of the main combustion chamber 14. The ignited waste is sent to the combustion stoker 16. The ignited waste also generates combustible gases due to pyrolysis. This combustible gas is sent by the primary air to the gas layer at the top of the main combustion chamber 14, where it flame-burns with the secondary air. The heat radiation accompanying this flame combustion further raises the temperature of the waste. A portion of the ignited waste is burned in the combustion stoker 16, and the remaining unburned portion is sent to the post-combustion stoker 17. The unburned waste is burned in the post-combustion stoker 17, and the incineration ash remaining after combustion is discharged to the outside through a chute 18.
[0118] The main combustion chamber 14 is connected to the radiation chamber 20, and the combustion exhaust gas generated by the combustion of the waste is sent to the radiation chamber 20. After being burned again in the radiation chamber 20, this combustion exhaust gas is led from the upper part of the radiation chamber 20 (first flue) through the second flue 21 to the third flue 22, and then is treated to be harmless in an exhaust gas treatment facility (not shown) before being released into the atmosphere. The radiation chamber 20, the second flue 21, and the third flue 22 form the exhaust gas passage 8 through which the exhaust gas from the incinerator 2 passes.
[0119] In the boiler 1, the substances volatilized during combustion and some of the incineration ash are carried along with the flow of the combustion exhaust gas to the radiation chamber 20, the second flue 21, and the third flue 22, and adhere to and accumulate on the superheating organ 4. Such highly corrosive combustion ash and the like have traditionally been a cause of corrosion of the high-temperature superheating organ 4.
[0120] When the second corrosion inhibitor is supplied to the flue, the corrosion inhibitor adheres to the inner surface of the flue and the surface of the superheating organ 4 together with the combustion ash containing corrosive particles floating in the flue, and adsorbs the corrosive particles in the combustion ash. This allows the corrosion inhibitor to suppress corrosion of the superheating organ 4 and the inner surface of the flue. The boiler 1 shown in Fig. 26 can be operated for a required period while supplying the second corrosion inhibitor, and the combustion ash obtained from the boiler 1 can be treated according to the above-described method to produce further corrosion inhibitor. In this way, the recovered combustion ash can be repeatedly treated and reused. EXAMPLES
[0121] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples.
[0122] [Example 1] A first slurry containing 2 kg of molten fly ash generated from a first waste treatment facility that treats waste by high-temperature melting and 10 kg of tap water was stirred and mixed for 10 minutes using four inclined paddle blades to dissolve water-soluble compounds contained in the molten fly ash, including Pb, Ca, Na, K, and Cl, and prepare a second slurry. The first waste treatment facility has a melting furnace for pyrolyzing and gasifying fuel, a combustion chamber for completely burning the pyrolysis gas generated in the melting furnace, an exhaust gas passage through which the combustion exhaust gas generated in the combustion chamber passes, and a superheater tube disposed in the exhaust gas passage, and is a waste treatment facility in which the first corrosion inhibitor obtained by the same method as that for producing the second corrosion inhibitor obtained in Example 3 described later is applied to the exhaust gas passage. In this example, the corrosion inhibitor is applied to the exhaust gas passage of the first waste treatment facility, and the first waste treatment facility is operated for one month, and the above-mentioned molten fly ash obtained from the first waste treatment facility is used as combustion ash. Table 1 shows an example of the components contained in the untreated molten fly ash generated from the first waste treatment facility and their contents (mass%). Each component was measured by X-ray fluorescence analysis, and the heavy metals Pb, Zn, and Cu were measured by ICP atomic emission spectrometry after wet decomposition. As shown in Table 1, the molten fly ash contains heavy metals Pb, Zn, and Cu, which are corrosion factors of boiler superheater tubes, Cl, and Ca, which is an inhibitor in the synthesis of corrosion inhibitors. It also contains Si and Al, which can be components of corrosion inhibitors, but it can be seen that the Si and Al contents are very low compared to the waste incineration ash, coal combustion ash, etc. used in Patent Document 1. In this embodiment, the target is molten fly ash and incineration fly ash having a Ca content in the range of 15% by mass to 25% by mass, a Si content in the range of 2.5% by mass to 6.0% by mass, an Al content in the range of 0.5% by mass to 4% by mass, a Pb content in the range of 0.3% by mass to 3% by mass, a Zn content in the range of 1.0% by mass to 6.0% by mass, a Cu content in the range of 0.01% by mass to 0.5% by mass, and a Cl content in the range of 10% by mass to 25% by mass.
[0123] [Table 1]
[0124] Next, the second slurry was subjected to solid-liquid separation to separate it into a filtrate and molten fly ash after water washing treatment. The elution rates of water-soluble components eluted in the filtrate obtained by solid-liquid separation of the second slurry are shown in Table 2. The elution amount of each component contained in the filtrate was measured by ICP atomic emission spectrometry. The elution rates were calculated using the following formula (1). Dissolution rate of water-soluble components (mass%) = each component contained in the filtrate (g) / each component contained in untreated molten fly ash (g) × 100... (1)
[0125] [Table 2]
[0126] From Table 2, it was confirmed that water-soluble compounds including Pb, Zn, Ca, Na, K, and Cl can be removed by washing the molten fly ash with water.
[0127] Next, a third slurry containing 2 kg of the recovered molten fly ash after the water washing treatment (including water that could not be separated by solid-liquid separation) and 5.0 kg of water was prepared by stirring and mixing the third slurry using four inclined paddle blades while maintaining the pH of the third slurry at 1.0, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, and 5.5, respectively, and adding 2 mol / L of hydrochloric acid to prepare a fourth slurry. If the third slurry was continued to be stirred and mixed even after the addition of hydrochloric acid was stopped, the alkali contained in the molten fly ash was gradually dissolved, and the pH of the third slurry increased. As a result, the pH of the third slurry became greater than 1.0, greater than 2.0, greater than 2.5, greater than 3.0, greater than 3.5, greater than 4.0, greater than 4.5, and greater than 5.5, respectively. Therefore, the third slurry was stirred and mixed while adding hydrochloric acid again, and 2 mol / L hydrochloric acid was supplied until the pH of the third slurry became constant. When the pH of the third slurry became constant, the addition of hydrochloric acid was stopped, and the slurry was stirred for 10 minutes.
[0128] Next, the fourth slurry was subjected to solid-liquid separation to separate it into a filtrate and molten fly ash after pickling treatment (pre-hydrothermal treatment intermediate). The elution rates of the acid-soluble components eluted in the filtrate obtained by solid-liquid separation of the fourth slurry are shown in Figures 2 to 7. The elution amount of each component contained in the filtrate was measured by ICP atomic emission spectrometry. The elution rates were calculated using the following formula (2). Dissolution rate of acid-soluble components (mass%) = each component contained in the filtrate (g) / each component contained in untreated molten fly ash (g) × 100...(2)
[0129] From the results of Figures 2 to 7, it was confirmed that by subjecting the molten fly ash after the water-rinsing treatment to an acid-rinsing treatment, it is possible to remove the heavy metals Pb, Zn, and Cu, as well as acid-soluble compounds including Ca, which could not be removed by the water-rinsing treatment. 2 to 7, it can be seen that when the pH of the fourth slurry is below pH=2.5, the elution rates of Si and Al, which are components of the corrosion inhibitor, increase sharply. When the pH of the fourth slurry is 2.5 or higher, the elution rates of Si and Al decrease. In particular, when the pH of the slurry is 3.5 or higher, and further, when the pH is between pH=4.0 and pH=5.5, the elution rates of Si and Al decrease sharply.
[0130] The molten fly ash after the acid treatment (intermediate before the hydrothermal treatment) was dried at 105°C for 24 hours, and the results of the component analysis of the sample are shown in Table 3 as Example 8. The components were measured by an energy dispersive X-ray analyzer (EDS).
[0131] [Table 3]
[0132] Next, 30 g of sodium orthosilicate was added to 270 g (dry weight) of the molten fly ash after the acid treatment, which was recovered by solid-liquid separation of the fourth slurry having a pH of pH = 4.0, and 2 mol / L of sodium hydroxide aqueous solution was added so that the ratio of the molten fly ash after the acid treatment (including sodium orthosilicate) to the sodium hydroxide aqueous solution (the mass ratio of the molten fly ash in a dry state) was 1 / 4, and these were stirred and mixed to prepare a fifth slurry. Next, the fifth slurry was stirred and mixed at 120° C. for 3 hours to synthesize a second corrosion inhibitor. Next, the fifth slurry was subjected to solid-liquid separation to separate it into a filtrate and a corrosion inhibitor. Next, tap water was added to the recovered corrosion inhibitor so that the ratio of the corrosion inhibitor to tap water (corrosion inhibitor (dry) / water) was 1 / 5 by mass, and the corrosion inhibitor was washed with water while the aqueous dispersion containing the corrosion inhibitor was subjected to solid-liquid separation. The resulting second corrosion inhibitor was dried at 105° C. for 24 hours.
[0133] [Example 2] To each of 240 g (dry weight) of the molten fly ash after the acid treatment recovered by solid-liquid separation of the fourth slurry pH=4.0 in Example 1, 60 g of sodium orthosilicate was added, and 2 mol / L of aqueous sodium hydroxide solution was added so that the ratio of the molten fly ash after the acid treatment (including sodium orthosilicate) to the aqueous sodium hydroxide solution (molten fly ash (dry)+sodium orthosilicate (dry) / aqueous sodium hydroxide solution) was 1 / 4 in terms of mass ratio, and these were stirred and mixed to prepare a fifth slurry. Next, the fifth slurry was stirred and mixed at 80° C. for 15 hours to synthesize the corrosion inhibitor. Next, the fifth slurry was subjected to solid-liquid separation to separate it into a filtrate and a corrosion inhibitor. Next, tap water was added to the recovered corrosion inhibitor so that the ratio of the corrosion inhibitor to tap water (corrosion inhibitor (dry) / water) was 1 / 5 by mass, and the second corrosion inhibitor was washed with water while the aqueous dispersion containing the corrosion inhibitor was subjected to solid-liquid separation.
[0134] [Example 3] To 270 g (dry weight) of the molten fly ash after the acid treatment recovered by solid-liquid separation of the slurry having a pH of 2.5 as the fourth slurry in Example 1, 30 g of sodium orthosilicate was added, and 2 mol / L of aqueous sodium hydroxide solution was added so that the ratio of the molten fly ash after the acid treatment (including sodium orthosilicate) to the aqueous sodium hydroxide solution ((molten fly ash (dry) + sodium orthosilicate (dry)) / aqueous sodium hydroxide solution) was 1 / 4 in terms of mass ratio, and these were stirred and mixed to prepare a fifth slurry. Next, the fifth slurry was stirred and mixed at 120° C. for 3 hours to synthesize the corrosion inhibitor. Next, the fifth slurry was subjected to solid-liquid separation to separate it into a filtrate and a corrosion inhibitor. Next, tap water was added to the recovered corrosion inhibitor so that the ratio of the corrosion inhibitor to tap water (corrosion inhibitor (dry) / water) was 1 / 5 by mass, and the second corrosion inhibitor was washed with water while the aqueous dispersion containing the corrosion inhibitor was subjected to solid-liquid separation.
[0135] [Example 4] A first slurry containing 2 kg of the same molten fly ash as that used in Example 1 and 10 kg of tap water was stirred and mixed for 10 minutes using four inclined paddle blades to dissolve water-soluble compounds contained in the molten fly ash, including Pb, Ca, Na, K, and Cl, to prepare a second slurry.
[0136] Next, the second slurry was subjected to solid-liquid separation to separate it into a filtrate and molten fly ash after washing with water.
[0137] Next, a third slurry containing 2 kg of the recovered molten fly ash after the water washing treatment (including water that could not be separated by solid-liquid separation) and 5.0 kg of water was prepared by stirring and mixing the third slurry using four inclined paddle blades while maintaining the pH of the third slurry at 2.5 by adding 1 mol / L of nitric acid, thereby preparing a fourth slurry. If the third slurry continues to be stirred and mixed after the addition of nitric acid is stopped, the alkali contained in the molten fly ash gradually dissolves, causing the pH of the third slurry to rise. As a result, the pH of the third slurry exceeds 2.5, so the third slurry is stirred and mixed again while adding nitric acid, and 1 mol / L of nitric acid is supplied until the pH of the third slurry becomes constant. When the pH of the third slurry becomes constant, the addition of nitric acid is stopped and the slurry is stirred for 10 minutes.
[0138] Next, the fourth slurry was subjected to solid-liquid separation to separate it into a filtrate and molten fly ash after pickling treatment (pre-hydrothermal treatment intermediate). The elution rates of the acid-soluble components eluted in the filtrate obtained by solid-liquid separation of the fourth slurry are shown in Figure 8. The elution amounts of each component contained in the filtrate were measured by ICP atomic emission spectrometry.
[0139] From the results in Fig. 8, it was confirmed that even when the molten fly ash after the water washing process was pickled with nitric acid, the heavy metals Pb, Zn, and Cu, and acid-soluble compounds including Ca, were removed to the same extent as when the molten fly ash was pickled with hydrochloric acid.
[0140] Next, 60 g of sodium orthosilicate was added to 240 g (dry weight) of the molten fly ash after the acid treatment recovered by solid-liquid separation of the fourth slurry, and 2 mol / L of aqueous sodium hydroxide solution was added so that the ratio of the molten fly ash after the acid treatment (including sodium orthosilicate) to the aqueous sodium hydroxide solution ((molten fly ash (dry) + sodium orthosilicate (dry))) / aqueous sodium hydroxide solution) was 1 / 4 in terms of mass ratio, and these were stirred and mixed to prepare a fifth slurry. Next, the fifth slurry was stirred and mixed at 80° C. for 15 hours to synthesize the corrosion inhibitor. Next, the fifth slurry was subjected to solid-liquid separation to separate it into a filtrate and a corrosion inhibitor. Next, tap water was added to the recovered corrosion inhibitor so that the ratio of the corrosion inhibitor to tap water (corrosion inhibitor (dry) / water) was 1 / 5 by mass, and the corrosion inhibitor was washed with water while the aqueous dispersion containing the corrosion inhibitor was subjected to solid-liquid separation. The resulting second corrosion inhibitor was dried at 105° C. for 24 hours.
[0141] [Example 5] In Example 1, 173 g of sodium metasilicate and 7 g of sodium aluminate were added to 120 g (dry weight) of the molten fly ash after the acid treatment recovered by solid-liquid separation of the fourth slurry, and a 2 mol / L aqueous sodium hydroxide solution was added so that the ratio of the molten fly ash after the acid treatment (including sodium metasilicate and sodium aluminate) to the aqueous sodium hydroxide solution (molten fly ash (dry) + sodium metasilicate (dry) + sodium aluminate (dry)) / aqueous sodium hydroxide solution) was 1 / 4 in terms of mass ratio, and these were stirred and mixed to prepare a fifth slurry. Next, the fifth slurry was stirred and mixed at 120° C. for 3 hours to synthesize the corrosion inhibitor. Next, the fifth slurry was subjected to solid-liquid separation to separate it into a filtrate and a corrosion inhibitor. Next, tap water was added to the recovered corrosion inhibitor so that the ratio of the corrosion inhibitor to tap water (corrosion inhibitor (dry) / water) was 1 / 5 by mass, and the corrosion inhibitor was washed with water while the aqueous dispersion containing the corrosion inhibitor was subjected to solid-liquid separation. The resulting second corrosion inhibitor was dried at 105° C. for 24 hours.
[0142] [Example 6] In the third step, the amount of hydrochloric acid added was adjusted to obtain the molten fly ash after acid treatment shown in Table 3. A 2 mol / L aqueous sodium hydroxide solution was added to 300 g of this molten fly ash so that the ratio of the molten fly ash after water washing treatment to the aqueous sodium hydroxide solution (molten fly ash (dry) / aqueous sodium hydroxide solution) was 1 / 4 in mass ratio when the molten fly ash was in a dry state, and these were stirred and mixed to prepare a slurry. Next, this slurry was stirred and mixed at 120°C for 3 hours to synthesize a corrosion inhibitor. Next, the slurry was subjected to solid-liquid separation to separate it into a filtrate and a corrosion inhibitor. Water was added to the recovered corrosion inhibitor so that the ratio of the corrosion inhibitor to water (corrosion inhibitor / water) was 1 / 5 by mass, and the corrosion inhibitor was washed with water while filtering the aqueous dispersion containing the corrosion inhibitor. The resulting second corrosion inhibitor was dried at 105° C. for 24 hours.
[0143] [Example 7] A first slurry containing 2 kg of molten fly ash different from that in Example 1 and 10 kg of tap water was stirred and mixed for 10 minutes using four inclined paddle blades to dissolve water-soluble compounds contained in the molten fly ash, including Pb, Ca, Na, K, and Cl, to prepare a second slurry.
[0144] Next, the second slurry was subjected to solid-liquid separation to separate it into a filtrate and molten fly ash after washing with water.
[0145] Next, a third slurry containing 2 kg of the recovered molten fly ash after the water washing treatment (including water that could not be separated by solid-liquid separation) and 5.0 kg of water was prepared by stirring and mixing the third slurry using four inclined paddle blades while maintaining the pH of the third slurry at 4.0 by adding 2 mol / L of hydrochloric acid, thereby preparing a fourth slurry. If the third slurry continues to be stirred and mixed after the addition of hydrochloric acid is stopped, the alkali contained in the molten fly ash gradually dissolves, causing the pH of the third slurry to rise. As a result, the pH of the third slurry exceeds 4.0, so the third slurry is stirred and mixed while adding hydrochloric acid again, and 2 mol / L of hydrochloric acid is supplied until the pH of the third slurry becomes constant. When the pH of the third slurry becomes constant, the addition of hydrochloric acid is stopped and the slurry is stirred for 10 minutes.
[0146] Next, the fourth slurry was subjected to solid-liquid separation to separate it into a filtrate and molten fly ash after pickling treatment (pre-hydrothermal treatment intermediate).
[0147] Next, 60 g of sodium orthosilicate was added to 240 g (dry weight) of the molten fly ash after the acid treatment recovered by solid-liquid separation of the fourth slurry, and 2 mol / L of aqueous sodium hydroxide solution was added so that the ratio of the molten fly ash after the acid treatment (including sodium orthosilicate) to the aqueous sodium hydroxide solution (molten fly ash (dry) + sodium orthosilicate (dry)) / aqueous sodium hydroxide solution) was 1 / 4 in terms of mass ratio, and these were stirred and mixed to prepare a fifth slurry. Next, the fifth slurry was stirred and mixed at 120° C. for 3 hours to synthesize the corrosion inhibitor. Next, the fifth slurry was subjected to solid-liquid separation to separate it into a filtrate and a corrosion inhibitor. Next, tap water was added to the recovered corrosion inhibitor so that the ratio of the corrosion inhibitor to tap water (corrosion inhibitor (dry) / water) was 1 / 5 by mass, and the corrosion inhibitor was washed with water while the aqueous dispersion containing the corrosion inhibitor was subjected to solid-liquid separation. The resulting second corrosion inhibitor was dried at 105° C. for 24 hours.
[0148] [Comparative Example 1] 1.2 kg of a 2 mol / L aqueous solution of sodium hydroxide was added to 300 g of the same molten fly ash as that used in Example 1, and the mixture was stirred and mixed to prepare a slurry. Next, the slurry was stirred and mixed for 3 hours at 120° C. to synthesize the corrosion inhibitor, and then the slurry was filtered to separate the filtrate and the corrosion inhibitor. Water was added to the recovered corrosion inhibitor so that the ratio of the corrosion inhibitor to water (corrosion inhibitor / water) was 1 / 5 by mass, and the corrosion inhibitor was washed with water while filtering the aqueous dispersion containing the corrosion inhibitor. The resulting corrosion inhibitor was dried at 105° C. for 24 hours.
[0149] [Comparative Example 2] 10 kg of water was added to 2 kg of the same molten fly ash used in Example 1, and the mixture was stirred and mixed for 10 minutes to prepare a slurry. Next, the slurry was subjected to solid-liquid separation to separate it into a filtrate and molten fly ash that had been washed with water. Next, 1.2 kg of a 2 mol / L aqueous solution of sodium hydroxide was added to 300 g of the recovered molten fly ash after the water washing treatment, and these were stirred and mixed to prepare a slurry. Next, the slurry was stirred and mixed for 3 hours at 120° C. to synthesize a corrosion inhibitor. Next, the slurry was subjected to solid-liquid separation to separate into a filtrate and a corrosion inhibitor. Water was added to the recovered corrosion inhibitor so that the ratio of the corrosion inhibitor to water (corrosion inhibitor / water) was 1 / 5 by mass, and the corrosion inhibitor was washed with water while filtering the aqueous dispersion containing the corrosion inhibitor. The resulting corrosion inhibitor was dried at 105° C. for 24 hours.
[0150] [Comparative Example 3] To 300 g (dry weight) of the acid-treated molten fly ash recovered by solid-liquid separation of the fourth slurry pH of Example 1 having a pH of 4.0, a 2 mol / L aqueous sodium hydroxide solution was added so that the mass ratio of the acid-treated molten fly ash to the aqueous sodium hydroxide solution (dry weight) / aqueous sodium hydroxide solution) was 1 / 4, and the mixture was stirred and mixed to prepare a fifth slurry. Next, the fifth slurry was stirred and mixed at 120° C. for 3 hours to synthesize the corrosion inhibitor. Next, the fifth slurry was subjected to solid-liquid separation to separate it into a filtrate and a corrosion inhibitor. Next, tap water was added to the recovered corrosion inhibitor so that the ratio of the corrosion inhibitor to tap water (corrosion inhibitor (dry) / water) was 1 / 5 by mass, and the corrosion inhibitor was washed with water while the aqueous dispersion containing the corrosion inhibitor was subjected to solid-liquid separation.
[0151] [Comparative Example 4] A first slurry containing 2 kg of the same molten fly ash as that used in Example 1 and 10 kg of tap water was stirred and mixed for 10 minutes using four inclined paddle blades to dissolve water-soluble compounds contained in the molten fly ash, including Pb, Ca, Na, K, and Cl, to prepare a second slurry.
[0152] Next, the second slurry was subjected to solid-liquid separation to separate it into a filtrate and molten fly ash after washing with water.
[0153] Next, a third slurry containing 2 kg of the recovered molten fly ash after the water washing treatment (including water that could not be separated by solid-liquid separation) and 5.0 kg of water was prepared by stirring and mixing the third slurry using four inclined paddle blades while maintaining the pH of the third slurry at 1.0 and adding 1 mol / L of nitric acid to prepare a fourth slurry. If the third slurry continues to be stirred and mixed even after the addition of nitric acid is stopped, the alkali contained in the molten fly ash gradually dissolves, and the pH of the third slurry increases. As the pH of the third slurry exceeds 1.0, the third slurry is stirred and mixed again while adding nitric acid, and 1 mol / L of nitric acid is supplied until the pH of the third slurry becomes constant. When the pH of the third slurry becomes constant, the addition of nitric acid is stopped and the slurry is stirred for 10 minutes.
[0154] Next, the fourth slurry was subjected to solid-liquid separation to separate it into a filtrate and molten fly ash after pickling treatment (pre-hydrothermal treatment intermediate).
[0155] Next, 60 g of sodium orthosilicate was added to 240 g (dry weight) of the molten fly ash after the acid treatment recovered by solid-liquid separation of the fourth slurry, and 2 mol / L of aqueous sodium hydroxide solution was added so that the ratio of the molten fly ash after the acid treatment (including sodium orthosilicate) to the aqueous sodium hydroxide solution ((molten fly ash (dry) + sodium orthosilicate (dry))) / aqueous sodium hydroxide solution) was 1 / 4 in terms of mass ratio, and these were stirred and mixed to prepare a fifth slurry. Next, the fifth slurry was stirred and mixed at 120° C. for 3 hours to synthesize the corrosion inhibitor. Next, the fifth slurry was subjected to solid-liquid separation to separate it into a filtrate and a corrosion inhibitor. Next, tap water was added to the recovered corrosion inhibitor so that the ratio of the corrosion inhibitor to tap water (corrosion inhibitor (dry) / water) was 1 / 5 by mass, and the corrosion inhibitor was washed with water while the aqueous dispersion containing the corrosion inhibitor was subjected to solid-liquid separation. The resulting corrosion inhibitor was dried at 105° C. for 24 hours.
[0156] [Comparative Example 5] In the third step of Example 1, the amount of hydrochloric acid added was adjusted to obtain molten fly ash with a Ca content of 18 wt% or more after the acid treatment. A 2 mol / L aqueous sodium hydroxide solution was added to 300 g (dry weight) of the molten fly ash after the acid treatment so that the mass ratio of the molten fly ash after the acid washing treatment to the aqueous sodium hydroxide solution was 1 / 4, and these were stirred and mixed to prepare a fifth slurry. Next, the fifth slurry was stirred and mixed at 120° C. for 3 hours to synthesize a corrosion inhibitor. Next, tap water was added to the recovered corrosion inhibitor so that the ratio of the corrosion inhibitor to the tap water (corrosion inhibitor (dry) / water) was 1 / 5 by mass, and the corrosion inhibitor was washed with water while the aqueous dispersion containing the corrosion inhibitor was subjected to solid-liquid separation.
[0157] [evaluation] (1) Identification of corrosion inhibitor crystals For the corrosion inhibitors obtained in Examples 1, 2, 3, 4, 5, 6, 7, and 8, and Comparative Examples 1, 2, 3, 4, and 5, crystals were identified and the crystal grain size was measured by powder X-ray diffraction (XRD). The crystal grain size was measured using the median diameter (d 50 Median diameter: particle diameter with a cumulative frequency of 50%. The results are shown in Table 4 below. Further, for Examples 1 to 8 and Comparative Example 5, a more detailed analysis was performed to identify the proportion (mass%) of the components contained in each Example. The results are shown in Table 5 below. The detailed components of each Example were analyzed by analyzing the results of X-ray diffraction measurement using the Rietveld method. The internal standard substance was corundum (α-Al 2 O 3 In Example 8 of Table 5, the components other than the amorphous phase contained 9.1 mass % calcium sulfate.
[0158] [Table 4]
[0159] [Table 5]
[0160] From the results in Table 4, peaks of calcium carbonate and calcium hydroxide were observed in Comparative Example 1, which was not subjected to water washing and pickling, Comparative Example 1, which was not subjected to water washing only, and Comparative Example 2, which was subjected to water washing only. In Comparative Example 2, which was subjected to water washing only, it is found that the Ca contained in the molten fly ash could not be sufficiently removed by water washing alone, and the Ca content after the addition of the Si source and the Al source was high at 29%, so that only peaks of calcium carbonate, calcium hydroxide, and anhydrous gypsum were observed. On the other hand, in Examples 1, 2, 3, 4, 5, 6, and 7, which were subjected to water washing and pickling, and the Ca content after the addition of the Si source and the Al source was reduced to 6 mass% or more and 16 mass% or less, and the Si+Al content after the addition of the Si source and the Al source was 11 mass% or more and 17 mass% or less, peaks of CSH, CASH, calcium phosphate, aluminate phase, magnesioferrite, calcium titanate, zinc oxide, and compounds of magnesium and zinc were observed.
[0161] As shown in Table 5, a more detailed analysis of Examples 1 to 8 revealed that zeolite, CSH, amorphous including CASH, calcium phosphate (Ca(PO 4 ) 6 (OH) 2 ), calcite or calcium carbonate (CaCO 3 ), aluminate phase (or calcium aluminate or a compound consisting of Ca, Al, and O: Ca 9 (Al 2 O 6 ) 3 C 3 A), hercynite (or a compound of Fe, Al, and O: FeAl 2 O 4 ), Gehlenite (or a compound of Ca, Al, Si, and O: FeAl 2 O 4 ), magnesium zinc iron oxide (a compound of Mg, Zn, Fe, and O), magnesioferrite (MgF 2 O 4 ), calcium titanate (CaTiO 3), zinc oxide (ZnO), and akermanite (or a compound of Ca, Mg, Si, and O) were found to be contained in the proportions (mass%) shown in Table 5.
[0162] (2) Corrosion test The test method involves preparing a test specimen by applying a mixture of simulated molten fly ash and corrosion inhibitor to the surface of a simulated superheater tube made of SUS310, placing this test specimen in a test room with a prescribed test temperature atmosphere, and supplying a test gas (combustion exhaust gas) of a prescribed composition at a prescribed flow rate for a prescribed time into the test room. The test time is 100 hours (a mixture of simulated molten fly ash and corrosion inhibitor is applied every 25 hours), and the test temperatures are 550°C and 500°C. The combustion exhaust gas conditions are HCl: 500 ppm, SO 2 : 50 ppm, O 2 : 5.0% by volume, H 2 O: 20% by volume, N 2 :72% by volume. The simulated molten fly ash was mixed with the comparative materials A (natural zeolite), B (quartz sand), C (calcium hydroxide), D (CSH synthesized using a reagent), and the corrosion inhibitors E (Example 1), F (Example 2), G (Example 3), H (Example 4), I (Example 5), J (Example 6), K (Comparative Example 1), L (Comparative Example 2), M (Comparative Example 3), and N (Comparative Example 4) under the following conditions: the simulated molten fly ash was mixed in an amount of 20 mg / cm2 relative to the surface area of the simulated superheater tube. 2 , and the comparative materials and corrosion inhibitors (Examples 1 to 6, Comparative Examples 1 to 4) were 6.6 mg / cm 2 After the simulated exhaust gas was allowed to flow for 100 hours, the weight loss rate (%) of the boiler superheater tube was calculated using the following formula (3). The corrosion test results at 550°C (the simulated superheater tube was made of SUS310S) are shown in Figure 9, and the corrosion test results at 500°C (the simulated superheater tube was made of SUS310S) are shown in Figure 10. The "without corrosion inhibitor" condition shown in Figures 9 and 10 is a condition in which no corrosion inhibitor was mixed with the molten fly ash. The weight loss rate of the simulated superheater tube in the "without corrosion inhibitor" condition is set to 100%. The smaller the weight loss rate, the less corrosion weight loss of the boiler superheater tube, indicating a higher corrosion inhibition effect. Weight loss rate (%) = (corrosion weight loss of boiler superheater tubes treated with corrosion inhibitors (mg / cm 2 ) / (corrosion weight loss of boiler superheater tubes with simulated molten fly ash only (mg / cm 2 )×100…(3) formula
[0163] 9 and 10, it can be confirmed that the use of the corrosion inhibitors of Examples 1, 2, 3, 4, 5, 6, 7, and 8 (pickled fly ash) has a higher corrosion inhibition effect on the simulated superheater tube than the use of natural zeolite, silica sand, and calcium hydroxide. It can also be confirmed that the corrosion inhibition effect is observed in Example 3, which does not contain zeolite, and CSH synthesized using a reagent. Furthermore, in Patent Document 2, the particle size of the corrosion-inhibiting particles is limited to 0.1 μm or more and less than 10 μm. However, from the test results shown in Figures 9 and 10 and the particle sizes shown in Table 4, it can be confirmed that even if the particle size of the corrosion inhibitor used in the present invention is 10 μm or more and 25 μm or less, it has a corrosion-inhibiting effect on a simulated superheater tube. Furthermore, it is found that even if Zn remains in the corrosion inhibitor, it does not affect the corrosion inhibition effect. The reason why the corrosion inhibitor according to the present invention exhibits a corrosion inhibitory effect even when the particle size is large will be explained together with the measurement results of the specific surface area explained in the test examples below. In Comparative Example 3, the total content of Si and Al in the starting material used in step 5 is 11% by mass or more (13.3% by mass), but the Ca content is 16% by mass or more (16.7% by mass). Therefore, CaCO 3 The production of CaCO contained in the molten fly ash recovered after step 5 increases. 3 , Ca(OH) 2 It can be seen that the corrosion inhibition effect is low. In Comparative Example 4, the Ca content in the starting material used in step 5 is 16 mass% or less (9.6 mass%), but the total content of Si and Al is less than 11 mass% (8.7 mass%), and the Si and Al necessary for forming CSH or CASH are insufficient, and CaCO 3The corrosion inhibition effect is low because the ratio of CaCO generated increases. 3 , CaSO 4 It can be seen that the corrosion inhibition effect is low.
[0164] Furthermore, the calcite content (mass%) and the weight loss rate (%) in the high-temperature corrosion test at 550°C described above were measured for the above-mentioned comparative agent A (natural zeolite), Example 1, Example 3, and Comparative Example 5, and the results are as follows: The weight loss rate of natural zeolite was 55.5%, that of Example 1 (calcium carbonate content: 5 mass%) was 42.3%, that of Example 3 (calcium carbonate content: 10.5 mass%) was 41%, and that of Comparative Example 5 (calcium carbonate content: 13.6 mass%) was 58.4%. From the above comparison, it is considered that the calcium carbonate content is preferably 13 mass % or less.
[0165] Next, in order to investigate the adsorption ability of the corrosion inhibitor, the cross section of the simulated superheater tube subjected to the corrosion test was investigated by EDS analysis. Figures 11 to 17 show color mapping of K, Na, Cl, Si, Al, and Ca in the cross section of the simulated superheater tube of Example 1. Figures 18 to 23 show color mapping of Cl, Si, Ca, Pb, and K in the cross section of the simulated superheater tube of Example 5. The color mapping of each component shows the concentration distribution. The top color of the bar showing the shades displayed on the right side of each figure indicates high concentration, and the bottom color (black) indicates low concentration, but since the scales are different for each component, it is not possible to compare the component proportions between components. Note that Si and Ca are constituent elements of the corrosion inhibitor, but are not contained in the simulated molten fly ash. K is a component that is not contained in the corrosion inhibitor, but is contained in the simulated molten fly ash. Cl is a component that is not contained in the corrosion inhibitor and is contained in the simulated molten fly ash and in the combustion exhaust gas. Pb is a component that is contained in the simulated molten fly ash.
[0166] From Figures 11 to 17, it can be seen that Cl, which is not contained in the corrosion inhibitor, is distributed in the same region as Si and Al. It can also be seen that K is distributed in the same region as Si and Al in the corrosion inhibitor that does not contain K. Na is a constituent element of the corrosion inhibitor and molten fly ash, but since the distribution of K has been confirmed in fly ash-based zeolite that does not contain K, it is thought that it also contains ash components. From this, it can be seen that the corrosion inhibitor adsorbs the corrosive components NaCl and KCl, the combustion exhaust gas component Cl, and the Cl-based gas generated by corrosion. 18 to 23, the corrosion inhibitor is PbCl 2 was also found to be adsorbed.
[0167] Next, to confirm the effectiveness of the corrosion inhibitor, qualitative and state analysis was performed by XPS on the corrosion products formed on the surface of the mock superheater test piece used in the corrosion test. The analyzed surfaces were near the outermost layer of the corrosion products, inside the corrosion product layer, and near the base material interface. The analyzed surfaces were surfaced by cutting the corrosion product layer obliquely in the depth direction using a SAICAS device. The analysis using the XPS device first involved a qualitative analysis, and then a state analysis was performed on the detected elements. FIG. 24 shows the results of an analysis of the corrosion product components inside the corrosion product layer when a simulated superheater tube (Alloy625) was coated with simulated molten fly ash and a mixture of the simulated molten fly ash and the corrosion inhibitor (Example 1) and then subjected to a corrosion test at 550°C for 100 hours. Fig. 25 shows the results of the analysis of the corrosion product components near the interface with the base material (simulated superheater tube) and the corrosion product when the simulated molten fly ash and the mixture of the simulated molten fly ash and the corrosion inhibitor (Example 1) were applied to a simulated superheater tube (Alloy625) and the corrosion test was carried out at 550°C for 100 hours. Table 6 shows the results of the state analysis of Cr and Ni.
[0168] [Table 6]
[0169] 24 and 25, the Cl ratio tends to be higher at the base metal interface side than in the corrosive material layer. This is particularly noticeable in the simulated superheater tube with only simulated molten fly ash, where the Cl ratio at the base metal interface side is about 30%, which is three times that in the corrosion product layer. When the corrosion inhibitor of Example 1 was used, the Cl ratio was about 4% at the base metal interface side and about 1% in the corrosion product layer, which shows that the Cl ratio is very small. It can be seen that the O ratio tends to be higher in the corrosion product layer and the outermost surface than the base metal interface side in the test piece with only simulated molten fly ash. On the other hand, when the corrosion inhibitor of Example 1 was used, the O ratio was about 50% both at the base metal interface side and in the corrosion product layer. From Table 6, in the case of the simulated superheater tube containing only simulated molten fly ash, the Cr on the base metal interface side was mainly oxide, and the Cr in the outermost layer and in the corrosion product layer also had oxide peak intensity, but the chloride (CrO 2 Cl 2 The Ni on the base material interface side showed peak intensities of oxides, but the chloride (NiCl 2 ), and the inner and outermost layers of the corrosion product layer are mainly oxides and hydroxides. On the other hand, when the corrosion inhibitor of Example 1 was used, Cr was present in the outermost surface and in the corrosion product layer as chlorides (CrO 2 Cl 2 ) was observed, but the outermost surface, the corrosion product layer, and the base metal interface were all dominated by Cr oxides. It can be seen that Ni is predominantly an oxide at the base metal interface.
[0170] 11 to 17, 18 and 19, 18 to 25, and Table 6 show that the corrosion inhibitor can reduce the corrosion factors such as NaCl, KCl, and HCl, Cl by using the corrosion inhibitor. 2 By adsorbing corrosive gas components such as these, the corrosive environment at the interface between the base material and the corrosion product is improved to a state in which oxide-based corrosion products are formed, and the chlorination reaction of Cr oxides and Ni oxides is suppressed, demonstrating the corrosion inhibition effect on the simulated superheater tube. The adsorption of the gas components and ash components described above is due to the adsorption ability of the corrosion inhibitor.
[0171] An experiment was carried out to recover heavy metals eluted during the acid washing treatment, using the filtrate obtained by solid-liquid separation of the fourth slurry in Example 1. The filtrate used in the test was from the third slurry having a pH of 4.0. 300 mL of the filtrate obtained by solid-liquid separation of the fourth slurry was taken, and 5 mol / L NaOH was added to the filtrate while stirring with a stirrer until the pH of the filtrate stabilized at pH=9.5 and pH=10.0.
[0172] Next, the filtrate was subjected to solid-liquid separation to separate the precipitate and the filtrate. The components of the resulting precipitate were measured by X-ray fluorescence spectroscopy, and the results are shown in Table 7 below. The contents of Pb, Zn, and Cu remaining in the filtrate were analyzed by ICP atomic emission spectrometry. The results are shown in Table 8 below.
[0173] [Table 7]
[0174] [Table 8]
[0175] It can be seen from Table 7 that the heavy metals eluted in the filtrate were successfully recovered, and from Table 8 that almost no heavy metals were contained in the filtrate after the sediment was recovered.
[0176] Table 9 shows the test conditions for Examples 1 to 7 and Comparative Examples 1 to 4, namely, the water washing treatment in the first step, the pickling treatment in the third step, and the alkaline hydrothermal treatment in the fifth step.
[0177] [Table 9]
[0178] Table 10 shows the proportions (wt%) of Si, Al and Ca in the intermediate before hydrothermal treatment.
[0179] [Table 10]
[0180] The BET specific surface area of the corrosion inhibitors of Examples 1 to 7 obtained in the above test results is shown in Table 11 below. 2 This is a gas adsorption method in which gas molecules such as nitrogen (N), argon (Ar), krypton (Kr), and carbon oxide (CO) are adsorbed onto solid particles, and the specific surface area of the solid particles is measured from the amount of adsorbed gas molecules. 2 ) was used to calculate the monomolecular adsorption amount (Vm) from the relationship between pressure (P) and adsorption amount (V) using the BET equation (Brunauer, Emmet and Teller's equation). Vm refers to the mass of gas molecules adsorbed on the surface of solid particles. Next, the specific surface area of the solid particles was calculated using the adsorption cross-section area (Am) of the gas molecules, etc. In addition to the corrosion inhibitors of Examples 1 to 7, the fly ash after pickling was used as the corrosion inhibitor of Example 8 to determine the BET specific surface area, and the BET specific surface area of Comparative Example 1 was also determined. Furthermore, the BET specific surface areas of natural zeolite A from Shimane Prefecture, natural zeolite B from Fukushima Prefecture, and natural zeolite C from Fukushima Prefecture were measured for comparison. The relationship between the BET specific surface areas based on these measurement results and the median diameters shown in Table 4 above is shown in Table 11 below for comparison.
[0181] [Table 11]
[0182] Referring to the median diameter in Table 11, the median diameters of Examples 1 to 8 are in the range of 10 μm or more and 25 μm or less, whereas the fly ash of Comparative Example 1 has a median diameter of less than 10 μm, and the median diameter of natural zeolite is distributed in a wide range of 3 to 36 μm. As explained above, in the technology described in Patent Document 2, the particle diameter of the corrosion-inhibiting particles is specified to be 0.1 μm or more and less than 10 μm. However, Examples 1 to 8 have a median diameter in the range of 10 μm or more and 25 μm or less, and show excellent corrosion-inhibiting effects despite their large particle diameters, which indicates that the corrosion inhibitor according to the present invention is a corrosion inhibitor that is completely different from the corrosion inhibitor described in Patent Document 2. The present inventor believes that the following explanation is relevant to the reason why the corrosion inhibitor according to the present invention exhibits excellent corrosion-inhibiting effects despite its large particle diameter.
[0183] As shown in Table 11, the BET specific surface area of the corrosion inhibitors of Examples 1 to 7 is 32 to 136 m 2 / g, which is extremely large compared to the BET specific surface area of natural zeolite and Comparative Example 1. It is described that the particle size of the corrosion inhibitor described in Patent Document 2 is small because, if the particle size of the corrosion inhibitor is large, corrosive substances pass through gaps between the corrosion inhibitors with large particle size and reach the overheating organ, and for this reason, the technology described in Patent Document 2 specifies the particle size as 0.1 μm or more and less than 10 μm. In contrast, the corrosion inhibitors of Examples 1 to 8 have large particle sizes but large specific surface areas, and therefore can efficiently adsorb corrosion-causing substances onto their surfaces. As a result, they can prevent corrosion-causing substances from reaching overheated organs, and are therefore thought to have excellent corrosion inhibition effects. In addition, it is believed that the corrosion inhibitors of Examples 1 to 8 are composed of corrosion inhibitor particles with large surface irregularities due to mutual adhesion of multiple components, and that the large surface irregularities provide excellent adsorption performance for corrosive substances.
[0184] Table 12 shows the results of calculating the molten fly ash reduction rate and the molten fly ash recovery rate (%) from the weight of the molten fly ash before the pickling treatment and the weight of the molten fly ash after the pickling treatment and drying at 105°C for 24 hours, in the cases of carrying out the pickling treatment at pH 2.5, pH 4.0, and pH 5.0 in producing the corrosion inhibitor of Example 1. Table 12 also shows the amount of Zn recovered calculated from the Zn content (%) / proportion in the Zn-containing material. In comparison with these, Table 12 shows the molten fly ash recovery rate in the conventional technology described in "Non-Patent Document Murayama et al.: Evaluation of Coal Ash and Incineration Ash as Zeolite Raw Materials, Resources and Materials, 117 (2001) No. 6" and the molten fly ash recovery rate in the case where the pH is not controlled.
[0185] [Table 12]
[0186] The Zn-containing material in Table 12 refers to a precipitate that is collected when an alkaline aqueous solution is added to the liquid fraction (filtrate after pickling) collected in the fourth step while stirring, the pH of the liquid fraction is adjusted to 9.0 to 10.5, and the pH-adjusted solution is separated into a liquid fraction and a precipitate. This precipitate is a raw material for crude zinc oxide. The Zn-containing material refers to a precipitate that is formed by dissolving metals such as Zn in the filtrate after pickling. The value of crude zinc oxide as a raw material is greater when the Zn content in the Zn-containing material is high. As shown in Table 12, the Zn recovery rate is greater at pH = 2.5, but the value as a crude zinc oxide raw material is higher at pH = 4.0 and pH = 5.0. As shown in Table 12, when pH=4.0 and pH=5.0, it is found that about 500 g of post-acid pickling corrosion inhibitor can be obtained from 1000 g of molten fly ash.
[0187] "HCl gas adsorption rate measurement test" To measure the HCl gas adsorption rate, 15 g of each of the corrosion inhibitors of Examples 1, 3, 5, and 7 and the natural zeolite shown in Table 11 were filled into a ceramic container in a tubular furnace, and the concentration of HCl: 500 ppm, SO 2 : 50 ppm, O 2 : 5.0% by volume, H 2 O: 20% by volume, N 2A simulated exhaust gas of 72% by volume was passed through at a specified flow rate. The temperature conditions were 450°C and 650°C, assuming the gas temperature range in which the corrosion inhibitor is supplied in the actual equipment. The gas flow time was set to 1 hour after the set temperature was reached, and the HCl gas adsorption rate was calculated from the ratio of the hydrogen chloride inlet concentration to the outlet concentration after passing through the corrosion inhibitor. The results are shown in Table 13 below.
[0188] [Table 13]
[0189] From the test results shown in Table 13, it was confirmed that when the corrosion inhibitors of Examples 1, 3, 5, and 7 were used, the HCl gas adsorption performance was higher than when the natural zeolites A, B, and C were used. It was also confirmed that Example 3, which does not contain zeolite, had a higher HCl gas adsorption performance than the natural zeolites A, B, and C. [Explanation of symbols]
[0190] 1...boiler, 2...combustion chamber, 3...exhaust gas passage, 4...superheater, 6, 7, 8...corrosion inhibitor supply device, 20...radiation chamber, 21...second flue, 22...third flue.
Claims
1. An acquisition step of acquiring combustion ash generated in a first waste treatment facility to which the first boiler corrosion inhibitor has been introduced, the combustion ash containing Ca, Al, and Si; A washing process for washing and pickling the combustion ash obtained in the obtaining process; and a manufacturing step of performing an alkali hydrothermal treatment on the combustion ash that has been subjected to the water washing treatment and the acid washing treatment in the cleaning treatment step to obtain a second corrosion inhibitor for a boiler. a method for producing a corrosion inhibitor for a boiler, comprising the steps of: adjusting the Ca content to 16 mass% or less when the Ca content contained in the combustion ash to be subjected to the alkaline hydrothermal treatment exceeds 16 mass%; and adding a Si source or an Al source when performing the alkaline hydrothermal treatment, so that the total content of Si and Al contained in the combustion ash to be subjected to the alkaline hydrothermal treatment is 11 mass% or more when the total content of Si and Al contained in the combustion ash to be subjected to the alkaline hydrothermal treatment is less than 11 mass%.
2. The average particle diameter (d 50 2. The method for producing a boiler corrosion inhibitor according to claim 1, wherein the particle size of the particles is 10 μm or more and 25 μm or less.
3. 3. The method for producing a corrosion inhibitor for a boiler according to claim 1, wherein the second corrosion inhibitor for a boiler obtained in the production step contains 40 mass % or more of amorphous matter.
4. In addition to the amorphous phase, the second corrosion inhibitor for boilers obtained in the production process is further 4. The method for producing a corrosion inhibitor for boilers according to claim 1, characterized in that at least one or more selected from the group consisting of calcium phosphate, calcium carbonate, aluminate phase, hercynite, zeolite, gehlenite, magnesioferrite, magnesium zinc iron ion oxide, calcium titanate, zinc oxide, and akermanite are contained.
5. 5. The method for producing a corrosion inhibitor for a boiler according to claim 1, wherein the second corrosion inhibitor for a boiler obtained in the production process is obtained by subjecting combustion ash that has been subjected to water washing and acid washing in the cleaning process to an alkaline hydrothermal treatment.
6. 6. The method for producing a corrosion inhibitor for a boiler according to claim 5, wherein an alkaline aqueous solution is used in the production process, and the second corrosion inhibitor for a boiler is obtained by washing away the alkaline aqueous solution.
7. The second boiler corrosion inhibitor obtained in the manufacturing process has a BET specific surface area of 90 m 2 7. The method for producing a boiler corrosion inhibitor according to claim 6, wherein the corrosion inhibitor has a molecular weight of 1.0 to 1.0 kg / g or more.
8. 5. The method for producing a corrosion inhibitor for a boiler according to claim 1, wherein the cleaning step comprises pickling the combustion ash obtained in the obtaining step.
9. The second boiler corrosion inhibitor obtained in the manufacturing process has a BET specific surface area of 60 m 2 9. The method for producing a corrosion inhibitor for boilers according to claim 8, wherein the corrosion inhibitor has a molecular weight of 1.0 to 1.0 kg / g or more.
10. The first waste treatment facility is a melting furnace; The combustion ash is molten fly ash containing heavy metals, 5. The method for producing a corrosion inhibitor for a boiler according to claim 1, wherein the cleaning step comprises pickling the combustion ash obtained in the obtaining step.
11. 5. The method for producing a corrosion inhibitor for a boiler according to claim 4, wherein in the cleaning treatment step, the combustion ash is subjected to an acid cleaning treatment to dissolve out Zn contained in the combustion ash.
12. The method for producing a corrosion inhibitor for a boiler according to claim 11, characterized in that the combustion ash that has been subjected to the acid washing treatment in the washing treatment step is in a slurry state, and the pH of the combustion ash is 2.5 or more and 5.5 or less.
13. The first waste treatment facility is a stoker furnace; The combustion ash is incineration fly ash, 5. The method for producing a corrosion inhibitor for a boiler according to claim 1, wherein the combustion ash obtained in the obtaining step is washed with water in the washing step.
14. The method for producing a corrosion inhibitor for a boiler according to any one of claims 1 to 13, characterized in that the cleaning treatment step is carried out once.
15. 15. The method for producing a corrosion inhibitor for a boiler according to any one of claims 1 to 14, characterized in that the first corrosion inhibitor for a boiler is obtained by subjecting combustion ash generated in the first waste treatment facility or combustion ash generated in a second waste treatment facility different from the first waste treatment facility to a water washing treatment or an acid washing treatment.
16. In the obtaining step, the corrosion inhibitor for a boiler obtained in the production step is used as the first corrosion inhibitor for a boiler, 16. The method for producing a corrosion inhibitor for a boiler according to claim 1, wherein the obtaining step, the cleaning treatment step, and the producing step are repeated.
17. 17. The method for producing a corrosion inhibitor for a boiler according to claim 1, wherein a content of calcium carbonate contained in the second corrosion inhibitor for a boiler obtained in the production process is 13 mass% or less.
18. A method for suppressing corrosion of a superheating device provided in an exhaust gas passage through which combustion exhaust gas of a boiler passes, comprising: A second boiler corrosion inhibitor manufactured by the manufacturing method according to any one of claims 1 to 17 is supplied into the exhaust gas passage. Methods for inhibiting boiler corrosion.
Citation Information
Patent Citations
Control device for resistance welding machine
JP1985046886A
Method for recycling waste incineration ash
JP1999207294A
Combustion apparatus, operation method of combustion apparatus and ash circulation system
JP2015190727A
Corrosion inhibitor for boilers, boiler and method for inhibiting corrosion of boiler
WO2014192313A1